Melt processable cellulose ester compositions, melts and melt molded articles made therefrom - Patents.com
Melt-processable plasticized cellulose ester compositions, incorporating cellulose acetate and aromatic sulfonate units, address the need for biodegradable and compostable disposable products by enhancing processability and achieving high biodegradation rates.
Patent Information
- Application Number
- JP2024547858
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-16
- Filing Date
- 2023-02-14
- Publication Date
- 2025-03-21
AI Technical Summary
There is a need for disposable consumer products that are biodegradable and compostable, while maintaining performance and melt processing properties, and incorporating a significant content of renewable, reused, and recycled materials.
The development of melt-processable plasticized cellulose ester compositions, specifically containing cellulose acetate, plasticizers, and aromatic sulfonate repeat units, which are suitable for forming biodegradable articles through melt processing.
These compositions offer improved processability and article properties, enabling the production of biodegradable articles that meet performance and environmental sustainability criteria, including high biodegradation rates under various composting conditions.
Smart Images

Figure 2025507556000001 
Figure 2025507556000002 
Figure 2025507556000003
Abstract
Description
[Background technology]
[0001] There are well-known problems worldwide with waste disposal, particularly with regard to the disposal of large amounts of consumer products such as plastics or polymers that are not considered biodegradable within acceptable time limits. There is a societal desire to incorporate these types of waste into new products through reuse, re-use or otherwise reducing the amount of waste in circulation or in landfills. This is especially true with regard to disposable plastic articles / materials.
[0002] As consumer sentiment regarding the environmental fate of single-use plastics such as straws, cutlery, takeaway cups, and plastic bags has become a global trend, plastic bans are being considered / enacted around the world in both developed and developing countries. For example, in the United States alone, bans range from plastic shopping bags to straws, cutlery, and clamshell containers. Others are taking even more extreme measures, as exemplified by the EU-wide list of 10 single-use items that will be banned, have their use restricted, or have increased producer responsibility mandated. As a result, industry leaders, brand owners, and retailers have made ambitious commitments to implement compostable and / or biodegradable materials going forward.
[0003] The use of biodegradable, disintegrable and / or compostable materials in the manufacture of such disposable articles is highly desirable from an environmental perspective, but presents special problems for article manufacturers. The majority of such articles have historically been manufactured using non-biodegradable, fossil fuel-based materials such as polystyrene, utilizing melt processing techniques such as casting, extrusion and injection molding, in which the material is melted into a flowable form, processed and cooled to form a functional article. In existing manufacturing systems, utilizing biodegradable raw materials such as some cellulose esters, including cellulose acetate, can be difficult without significant equipment replacement, modification or retrofitting costs. Furthermore, changes in processing conditions that may be required by using biodegradable materials such as cellulose esters can adversely affect efficiency and material yield. In addition, the melt processing step to convert cellulose ester compositions into useful articles requires heating the formulation to temperatures that can result in color formation, loss of compositional ingredients such as plasticizers and loss of molecular weight of the polymer, all of which affect the thermal stability, toughness, flexibility and other performance parameters of the final article. Also, because biodegradation is generally a surface-driven phenomenon, the desire to meet biodegradability and compostability standards can drastically limit the thickness desired for article strength.
[0004] There remains an unmet market need for disposable consumer products that have suitable performance and melt processing characteristics for their intended use, and that are compostable and / or biodegradable.
[0005] It would also be beneficial to provide a product having such characteristics that also has a significant content of renewable, reclaimed and / or reused materials. Summary of the Invention
[0006] Applicants have unexpectedly discovered that certain melt-processable plasticized cellulose ester compositions are surprisingly advantageous for use in the manufacture of melt-formed biodegradable articles and biodegradable article components, with unexpected processability and article property advantages.
[0007] In one aspect, the present invention is directed to a melt-processable plasticized cellulose ester composition. The melt-processable cellulose acetate composition of the present invention comprises: (i) a cellulose ester; (ii) a plasticizer; and (iii) a polymer comprising aromatic sulfonate repeat units.
[0008] In another aspect, the present invention is directed to a cellulose ester melt, which is particularly useful for forming melt-molded articles. The cellulose ester melt of the present invention comprises (i) cellulose acetate; (ii) a plasticizer; and (iii) a polymer comprising aromatic sulfonate repeat units.
[0009] In yet another aspect, the present invention is directed to a melt-formed biodegradable article comprising, formed from, or prepared using a melt-processable plasticized cellulose ester composition comprising (i) a cellulose ester; (ii) a plasticizer; and (iii) a polymer comprising aromatic sulfonate repeat units, or a cellulose ester melt comprising (i) a cellulose ester; (ii) a plasticizer; and (iii) a polymer comprising aromatic sulfonate repeat units.
[0010] In various interrelated aspects and embodiments, the present invention is generally directed to melt-processable compositions, including foamable compositions; melts; foams; articles, including melt-molded articles, and articles that include, are formed from, or are prepared from melt-processable compositions and related foamable compositions. Those skilled in the art will recognize and understand that elements or features used to describe one aspect or embodiment may be applicable and useful in describing other embodiments. In a non-limiting example, the description of cellulose esters explicitly described in the context of the compositions of the present invention is also applicable and useful in describing cellulose esters in the context of melts, compositions (including extruded, molded, thermoformed, or foamable compositions) and articles of the present invention. Thus, descriptions and disclosures related to elements or features of one aspect or embodiment of the present invention are expressly relied upon to describe and support these elements or features in other aspects or embodiments.
[0011] In the following various aspects and embodiments, the present invention is described in detail as the cellulose acetate composition comprising cellulose acetate.However, it is understood that the description related to such specific embodiment is also expressly relied upon to describe and support the embodiment more broadly directed to the cellulose ester composition comprising cellulose ester.
[0012] The present application also discloses, in various aspects, additional compositions, melts, articles, and methods. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In a first aspect, the present invention is directed to a melt-processible plasticized cellulose ester composition. The melt-processible cellulose ester composition of the present invention comprises: (i) a cellulose ester; (ii) a plasticizer; and (iii) a polymer comprising aromatic sulfonate repeat units.
[0014] The cellulose ester of the present invention can generally be described as comprising one or more carboxylic acid cellulose esters, for example, as described in commonly assigned U.S. Patent No. 5,929,229, the contents and disclosure of which are incorporated herein by reference.Non-limiting examples of cellulose ester include cellulose acetate, cellulose propionate, cellulose butyrate, so-called mixed acid esters, such as cellulose acetate propionate and cellulose acetate butyrate, and combinations thereof.In one or more embodiments, cellulose ester is selected from the group consisting of cellulose acetate, cellulose acetate propionate, or cellulose acetate butyrate, and combinations thereof.
[0015] In one or more embodiments, the cellulose ester comprises, consists essentially of, or consists of cellulose acetate. In one or more embodiments, the cellulose acetate may be present in the melt-processable plasticized cellulose acetate composition in an amount of 50% to 97% by weight, or 55% to 95% by weight, or 60% to 90% by weight, based on the total weight of the melt-processable plasticized cellulose ester composition. Cellulose acetates that may be useful in the present invention generally have the structure:
[0016] [ka]
[0017] [In the formula, R 1 , R 2 , and R 3 are independently selected from the group consisting of hydrogen and acetyl. Repeat units of 0.01 to 0.01. For cellulose esters, the substitution level is usually expressed by the degree of substitution (DS), which is the average number of non-OH substituents per anhydroglucose unit (AGU). Generally, conventional cellulose contains three hydroxyl groups for each AGU unit to which cellulose acetate is substituted; therefore, the cellulose acetate DS has a value between zero and 3. Natural cellulose, even after pulping and purification, is a large polysaccharide with a degree of polymerization of 250 to 5,000, so the assumption that the maximum DS is 3.0 is approximately correct. Since DS is a statistical average, a value of 1 does not guarantee that all AGUs have one substituent. In some cellulose acetates, some have unsubstituted anhydroglucose units, some have two substituents, and some have three substituents, and typically the DS value is a non-integer. The total DS is defined as the average number of all substituents per anhydroglucose unit. The degree of substitution per AGU cellulose acetate also refers to a specific substituent, such as hydroxyl or acetyl, for example. In embodiments, n is an integer ranging from 25 to 250, or 25 to 200, or 25 to 150, or 25 to 100, or 25 to 75. The cellulose acetate useful in embodiments of the present invention has a degree of substitution ranging from 1.0 to 2.5. In some embodiments, the cellulose acetate may have an average degree of substitution of at least about 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45 or 1.5 and / or no more than about 2.5, 2.45, 2.4, 2.35, 2.3, 2.25, 2.2, 2.15, 2.1, 2.05, 2.0, 1.95, 1.9, 1.85, 1.8 or 1.75. In some embodiments, the cellulose acetate may have an average degree of substitution from 0.7 to 2.9, or from 1.1 to 2.7, or from 1.1 to 2.6, or from 1.1 to 2.5, or from 2.0 to 2.6, or from 1.7 to 2.6.
[0018] In an embodiment of the present invention, the cellulose acetate has at least two anhydroglucose rings, and the cellulose acetate has at least 50 to 5,000 anhydroglucose rings, or at least 50 to less than 150 anhydroglucose rings. The number of anhydroglucose units per molecule is defined as the degree of polymerization (DP) of the cellulose acetate. In an embodiment, the cellulose acetate may have an intrinsic viscosity (IV) of about 0.2 to about 3.0 deciliters per gram, or about 0.5 to about 1.8, or about 1 to about 1.5, measured at a temperature of 25° C. for a 0.25 gram sample in 100 ml of a 60 / 40 by weight solution of phenol / tetrachloroethane. In an embodiment, the cellulose acetate useful in some embodiments may have a DS / AGU of about 1 to about 2.5, or less than 1 to 2.2, or less than 1 to 1.5, and the substituted ester is acetyl. The cellulose acetate useful in some embodiments may include cellulose diacetate and cellulose triacetate.
[0019] The cellulose esters useful in the present invention, specifically cellulose acetate, may be biodegradable. The term "biodegradable" generally refers to the biological transformation and consumption of organic molecules. Biodegradability is an inherent property of the material itself, and the material cellulose acetate exhibits different degrees of biodegradability depending on the specific conditions to which it is exposed. The term "disintegrability" refers to the tendency of a material to physically dissociate into smaller pieces when exposed to certain conditions. Disintegration depends on both the physical size and configuration of the material itself as well as the article being tested. Ecotoxicity measures the effect of the material on plant life, and the heavy metal content of the material is determined in accordance with procedures set forth in standard test methods. The melt processable compositions and melts of the present invention may be biodegradable in one or more embodiments.
[0020] The cellulose ester of the present invention can be produced by any method known in the art.Generally, the example of the process of producing cellulose ester is taught in Kirk-Othmer, Encyclopedia of Chemical Technology, 5th edition, vol. 5, Wiley-Interscience, New York (2004), pp. 394-444.The starting material cellulose for producing cellulose acetate can be obtained in various grades and from sources such as cotton linters, softwood pulp, hardwood pulp, corn fiber and other agricultural sources, and bacterial cellulose, among others.
[0021] One method of producing cellulose acetate is the esterification of cellulose by mixing it with an appropriate organic acid, an acid anhydride, and a cellulose catalyst. The cellulose is then converted to a cellulose triester. Ester hydrolysis is then carried out by adding a water-acid mixture to the cellulose triester, and the cellulose acetate is then filtered to remove any gel particles or fibers. Water is then added to the mixture to precipitate the cellulose ester. The cellulose ester can then be washed with water to remove reaction by-products, followed by dehydration and drying.
[0022] The cellulose triesters that are hydrolyzed have three acetyl substituents. These cellulose esters can be prepared by a number of methods known to those skilled in the art. For example, the cellulose esters can be prepared by the methods described below. 2 SO 4 The cellulose triesters may be prepared by the heterogeneous acylation of cellulose in a mixture of a carboxylic acid and anhydride in the presence of a cellulose catalyst such as LiCl / DMAc or LiCl / NMP. The cellulose triesters may also be prepared by the homogeneous acylation of cellulose dissolved in a suitable solvent such as LiCl / DMAc or LiCl / NMP.
[0023] Those skilled in the art will understand that the commercial term cellulose triester also includes the cellulose ester that is not fully substituted with acyl groups.For example, cellulose triacetate is commercially available from Eastman Chemical Company, Kingsport, TN, USA, and typically has a DS of about 2.85 to about 2.99.
[0024] After esterification of cellulose to triester, some of the acyl substituents can be removed by hydrolysis or alcoholysis to give secondary cellulose esters.As mentioned above, depending on the specific method used, the distribution of acyl substituents can be random or non-random.Secondary cellulose esters can also be prepared directly by using a limited amount of acylating reagent without hydrolysis.This process is particularly useful when the reaction is carried out in a solvent that dissolves cellulose.All of these methods produce cellulose esters that are useful in the present invention.
[0025] In one embodiment, or in combination with any of the mentioned embodiments, the cellulose acetate of the present invention is cellulose diacetate. The cellulose diacetate may have a polystyrene-equivalent number average molecular weight (Mn) of about 10,000 to about 100,000, as measured by gel permeation chromatography (GPC) using NMP as a solvent and converted into polystyrene Mn according to ASTM D6474. In another aspect or embodiment of the present invention described herein, the melt-processable biodegradable cellulose acetate composition of the present invention may be a cellulose acetate composition of the present invention, as measured by gel permeation chromatography (GPC) using NMP as a solvent and converted into polystyrene Mn according to ASTM D6474. or less than 10,000 to 55,000; or less than 10,000 to 50,000; or less than 10,000 to 45,000; or less than 10,000 to 40,000; or less than 10,000 to 30,000; or less than 20,000 to 60,000; or less than 20,000 to 55,000; or less than 10,000 to 50,000; or less than 10,000 to 45,000; or less than 10,000 to 40,000; or less than 10,000 to 30,000; or less than 20,000 to 60,000; or less than 20,000 to 55,000; or 20,000 to 50,000; or less than 20,000 to 50,000; or less than 20,000 to 45,000; or 20,000 to 40,000; or 20,000 to 35,000; or 20,000 to 30,000; or less than 30,000 to 60,000; or less than 30,000 to 55,000; or 30,000 to 50,000; or less than 30,000 to 50,000; or less than 30,000 to 45,000; or 30,000 to 40,000; or 30,000 to 35,000. In embodiments, the cellulose acetate may have a number average molecular weight (Mn) of 100,000 or less, or 90,000 or less, calculated as polystyrene, as measured using gel permeation chromatography using N-methyl-2-pyrrolidone (NMP) as a solvent.In some cellulose acetates, the biodegradable cellulose acetates may have an Mn of at least about 10,000, at least about 20,000, 25,000, 30,000, 35,000, 40,000, or 45,000 and / or no more than about 100,000, no more than 95,000, no more than 90,000, no more than 85,000, no more than 80,000, no more than 75,000, no more than 70,000, no more than 65,000, no more than 60,000, or no more than 50,000.
[0026] The most common commercial secondary cellulose esters are prepared by first acid-catalyzed heterogeneous acylation of cellulose to form cellulose triester. After obtaining a homogeneous solution of cellulose triester in the corresponding carboxylic acid, the cellulose triester is then subjected to hydrolysis until the desired degree of substitution is obtained. After isolation, random secondary cellulose esters are obtained. That is, the relative degree of substitution (RDS) at each hydroxyl is approximately equal.
[0027] In an embodiment of the present invention, cellulose acetate can be prepared by converting cellulose to cellulose esters using reactants obtained from recycled materials, such as recycled plastic-containing syngas sources. In an embodiment, such reactants can be cellulose reactants including organic acids and / or acid anhydrides used in esterification or acylation reactions of cellulose, such as those discussed herein.
[0028] The cellulose acetate of the present invention may be produced in any physical form that is desirable for downstream processing into compositions, melts and useful articles.In one or more embodiments, the biodegradable melt-stable cellulose acetate is in the form of powder.In one or more embodiments, the biodegradable melt-stable cellulose acetate is in the form of flakes or pellets.
[0029] In one or more embodiments, the melt-processable cellulose acetate composition comprises at least one recycled cellulose acetate.In one or more embodiments, the recycled cellulose acetate comprises at least one substituent on the anhydroglucose unit (AU) derived from recycled-containing materials, such as recycled plastic-containing syngas.Recycled cellulose acetate and methods for their manufacture are described, for example, in the assignee's PCT Publications WO2020 / 242921; WO2021 / 061918A1; WO2021 / 092296A1 and US Patent Publication No. 2020 / 0247910, all of which are expressly incorporated herein by reference.
[0030] In the embodiment of the melt-processable plasticized cellulose ester composition of the present invention comprises cellulose acetate, the composition may further comprise one or more additional cellulose esters.Non-limiting examples of such additional cellulose esters include cellulose propionate, cellulose butyrate, and so-called mixed acid esters, such as cellulose acetate propionate (CAP) and cellulose acetate butyrate (CAB).In the embodiment of the melt-processable plasticized cellulose ester composition of the present invention comprises cellulose acetate, the additional cellulose ester may comprise a second cellulose acetate that is different from the first cellulose acetate by one or more characteristics, such as degree of substitution (DS), glass transition temperature, intrinsic viscosity, acid value, hydroxyl value, bulk density, molecular weight, etc.
[0031] The cellulose ester may be present in the melt-processable plasticized cellulose ester composition in an amount of 1% to 99% by weight, based on the total weight of the composition. In one or more embodiments, the cellulose ester is present in an amount of at least 50% by weight, based on the total weight of the composition. One skilled in the art will appreciate that the amount of cellulose ester in the composition may vary based on a variety of factors, including, but not limited to, desired composition target properties such as crystallinity, toughness, elongation, adhesion, melt strength factor, etc. In one or more embodiments, the cellulose ester is present in an amount of at least 50% by weight, based on the total weight of the composition. In one or more embodiments, the cellulose ester is present in an amount of up to 70% by weight, based on the total weight of the composition. In one or more embodiments, the cellulose ester is present in an amount of up to 60% by weight, based on the total weight of the composition. In one or more embodiments, the cellulose ester is present in the biodegradable composition in an amount of up to 30% by weight, based on the total weight of the composition, or up to 20% by weight, based on the total weight of the composition, or up to 10% by weight, based on the total weight of the composition.
[0032] The melt-processable cellulose acetate composition of the present invention further comprises a plasticizer.The plasticizer may be used alone or in combination of two or more.The plasticizer may be generally described as a processing aid that can reduce, for example, the melting temperature, glass transition temperature (Tg) and / or melt viscosity of the cellulose acetate present in the composition.
[0033] In embodiments, the plasticizer is a biodegradable plasticizer. Some examples of biodegradable plasticizers include triacetin, tripropoinin, triethyl citrate, acetyl triethyl citrate, polyethylene glycol, benzoate-containing plasticizers such as Benzoflex™ plasticizer series, poly(alkyl succinates) such as poly(butyl succinate), polyethersulfone, adipate-based plasticizers, soybean oil epoxides such as Paraplex™ plasticizer series, sucrose-based plasticizers, dibutyl sebacate, tributyrin, Resoflex™ series plasticizers, triphenyl phosphate, glycolate, polyethylene glycol esters and ethers, 2,2,4-trimethylpentane-1,3-diylbis(2-methylpropanoate), polycaprolactone, and combinations thereof. In one or more embodiments, the plasticizer includes plasticizers with recycled content. Plasticizers having recycled content are generally described in WO2021092321A1, assigned to the assignee of the present invention, the contents and disclosure of which are expressly incorporated by reference herein.
[0034] In an embodiment, the plasticizer is a food-compatible plasticizer. The term "food-compatible" means that the plasticizer is compatible with applicable food additive and / or food contact regulations that are permitted for use or recognized as safe by at least one (national or regional) food safety regulatory agency (or organization). Food-compatible materials may include materials listed in 21 CFR Food Additive Regulations or other generally recognized as safe (GRAS) materials by the US FDA. In an embodiment, the food-compatible plasticizer is triacetin. In embodiments, examples of food compatible plasticizers that may be considered include triacetin, triethyl citrate, polyethylene glycol, benzoic acid esters (e.g., Benzoflex), propylene glycol, acetylated triethyl citrate, acetyl tributyl citrate, polymeric plasticizers (e.g., Admex), tripropionin, tributyrin, Saciflex, poloxamer copolymers, polyethylene glycol esters and ethers (e.g., PEG succinate), adipic acid esters (e.g., diisobutyl adipate), polyvinylpyrrolidone, glycerin tribenzoate, and combinations thereof. In one or more embodiments, the plasticizer may be selected from the group consisting of triacetin, polyethylene glycol having an average weight average molecular weight of 300 to 1000 Da, and combinations thereof.
[0035] The melt-processable cellulose ester composition of the present invention can be plasticized. Thus, plasticizer can be present in a plasticizing amount. The phrase "plasticizing amount" includes the amount of plasticizer sufficient to plasticize the cellulose ester present in the melt-processable cellulose ester composition, and facilitate the formation of melt and the melt processing of the melt into a useful melt-molded article. Those skilled in the art will understand that the specific amount of plasticizer that can constitute "plasticizing amount" can depend on many factors, such as the identity and amount of cellulose ester present in the composition and the identity of other additives or ingredients. For example, the presence of a compatible polymer, solvent, and certain processing aids such as foaming agent in the composition can reduce the amount of plasticizer required to plasticize cellulose acetate.
[0036] In embodiments, the plasticizer may be present in an amount sufficient to allow the melt-processable plasticized cellulose ester composition to be melt-processed (or thermoformed) into a useful article, such as a disposable plastic article, in conventional melt processing equipment. The amount of plasticizer may therefore vary based on factors including the type of thermal or melt processing used to make the article from the composition. Non-limiting processing examples include extrusion, such as profile extrusion and sheet extrusion; injection molding; compression molding; blow molding; thermoforming, etc. Thus, the articles that include the composition or are formed from the composition or can be prepared using the composition may include extrusion articles, such as profile extrusion articles and sheet extrusion articles; injection molding articles; compression molding articles; blow molding articles; thermoforming articles, etc.
[0037] In embodiments, the melt processable plasticized cellulose ester composition may contain from 1 wt.% to 40 wt.%, or from 5 wt.% to 40 wt.%, or from 5 wt.% to 30 wt.%, or from 10 wt.% to 40 wt.%, or from 13 wt.% to 40 wt.%, or from 15 wt.% to 50 wt.%, or from 15 wt.% to 40 wt.%, or from 17 wt.% to 20 wt.%, or from 20 wt.% to 25 wt.%, or from 25 wt.% to 30 wt.%, or from 30 wt.% to 40 wt.%, or from 30 wt.% to 40 wt.%, or from 40 wt.% to 50 wt.%, or from 40 wt.% to 50 wt.%, or from 50 wt.% to 50 wt.%, or from 50 wt.% to 50 wt.%, or from 60 wt.% to 70 wt.%, or from 70 wt.% to 80 wt.%, or from 80 wt.% to 100 wt.%, all based on the total weight of the melt processable plasticized cellulose ester composition. 40wt%, or 20wt% to 40wt%, or 25wt% to 40wt%, or 5wt% to 35wt%, or 10wt% to 35wt%, or 13wt% to 35wt%, or 15wt% to 35wt%, or more than 15wt% to 35wt%, or 17wt% to 35wt%, or 20wt% to 35wt%, or 5wt% to 30wt%, or 10wt% to 30wt%, or 13wt% to 30wt%, or is 15wt%~30wt%, or more than 15wt%~30wt%, or 17wt%~30wt%, or 5wt%~25wt%, or 10wt%~25wt%, or 13wt%~25wt%, or 15wt%~25wt%, or more than 15wt%~25wt%, or 17wt%~25wt%, or 5wt%~20wt%, or 10wt%~20wt%, or 13wt%~20wt%, or 15wt% It may be contained in an amount of up to 20wt%, or greater than 15wt% to 20wt%, or 17wt% to 20wt%, or 5wt% to 17wt%, or 10wt% to 17wt%, or 13wt% to 17wt%, or 15wt% to 17wt%, or greater than 15wt% to 17wt%, or less than 5wt% to 17wt%, or less than 10wt% to 17wt%, or less than 13wt% to 17wt%, or less than 15wt% to 17wt%.
[0038] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition of the present application has a melt-processible plasticized cellulose ester composition that is 10% to 150%, or 30% to 150%, or 50% to 150%, or 70% to 150%, or 90% to 150%, or 110% to 150%, or 10% to 130%, or 30% to 130%, or 50% to 130%, or 70% to 130%, or 90% to 150%, or 110% to 150%, or 10% to 130%, or 30% to 130%, or 50% to 130%, or 70% to 130%, or 90% to 150%, or 110% to 150%, or 10% to 130%, or 30% to 130%, or 50% to 130%, or 70% to 130%, or 110% to 150%, or 10% to 13 ... and exhibiting a strain hardening ("SH") in the range of 30%, or 110%-130%, or 10%-110%, or 30%-110%, or 50%-110%, or 70%-110%, or 90%-110%, or 10%-90%, or 30%-90%, or 50%-90%, or 70%-90%, or 10%-70%, or 30%-70%, or 50%-70%, or 10%-50%, or 30%-50%, or 10%-30%, where SH is determined by the procedures disclosed herein (i.e., pages 86-88). In one class of this embodiment, the polymer comprising aromatic sulfonate repeat units is a sulfonated polyester as disclosed and described herein.
[0039] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition of the present application exhibits a maximum areal draw ratio ("Max ADR") in the range of 10% to 50%, or 20% to 50%, or 30% to 50%, or 40% to 50%, or 30% to 40%, or 20% to 40%, or 20% to 30%, or 10% to 40%, or 10% to 30%, or 10% to 20%, relative to a melt-processible cellulose ester composition not including a polymer containing aromatic sulfonate repeat units, the Max ADR being determined by the procedures disclosed herein (i.e., pages 85-86). In one class of this embodiment, the polymer containing aromatic sulfonate repeat units is a sulfonated polyester as disclosed and described herein.
[0040] The melt-processible plasticized cellulose ester composition comprises a polymer comprising aromatic sulfonate repeat units. The phrase "polymer comprising aromatic sulfonate repeat units" refers to a polymer comprising at least one aromatic moiety having a pendant sulfonate group, as exemplified below:
[0041] [ka]
[0042] [In the formula, R is a residue containing an aromatic structure, and M is a monovalent cation.] is intended to describe a material comprising: In one or more embodiments, R is selected from the group consisting of isophthalic acid residues, terephthalic acid residues, and naphthalene residues; In one or more embodiments, M is selected from the group consisting of Li, Na, Ca, K, Zn, and Mg.
[0043] The term "polymer" is intended to include materials that contain or are formed from repeating units and have an intrinsic viscosity, hereinafter abbreviated as "Ih.V", of at least 0.1 dL / g, measured in a 60 / 40 parts by weight solution of phenol / tetrachloroethane solvent at 20° C. and at a concentration of 0.5 g of material in 100 mL of solvent.
[0044] In one or more embodiments, the polymer comprising aromatic sulfonate repeat units is present in an amount by weight, based on the total weight of the melt-processible plasticized cellulose ester composition, of from 0.1 wt% to 50 wt%, or from 0.1 wt% to 10 wt%, or from 0.1 wt% to 20 wt%, or from 0.1 wt% to 30 wt%, or from 0.1 wt% to 40 wt%, or from 1 wt% to 50 wt%, or from 1 wt% to 10 wt%, or from ... It is present in an amount of 1wt%-20wt% or 1wt%-30wt% or 1wt%-40wt% or 10wt%-50wt% or 10wt%-20wt% or 10wt%-30wt% or 10wt%-40wt% or 20wt%-50wt% or 20wt%-30wt% or 20wt%-40wt% or 30wt%-50wt% or 30wt%-40wt% or 40wt%-50wt%.
[0045] In one or more embodiments, the aromatic sulfonate repeat units are present in the polymer in an amount of 1 mol% to 50 mol%. In one or more embodiments, the aromatic sulfonate repeat units are present in the polymer in an amount of 1 mol% to 10 mol%, or 1 mol% to 20 mol%, or 1 mol% to 30 mol%, or 1 mol% to 40 mol%, or 10 mol% to 20 mol%, or 10 mol% to 30 mol%, or 10 mol% to 40 mol%, or 10 mol% to 50 mol%, or 20 mol% to 30 mol%, or 20 mol% to 40 mol%, or 20 mol% to 50 mol%, or 30 mol% to 40 mol%, or 30 mol% to 50 mol%, or 40 mol% to 50 mol%, or 15 mol% to 25 mol%.
[0046] In one or more embodiments, the polymer comprising aromatic sulfonate repeat units has the formula:
[0047] [ka]
[0048] wherein M is a monovalent cation selected from the group consisting of Li, Na, Ca, K, Zn, and Mg. The compound may be a polymer containing the repeating unit:
[0049] In one or more embodiments, the polymer comprising aromatic sulfonate repeat units may be a sulfonated polyester. In one or more embodiments, the sulfonated polyester may be represented by the formula
[0050] [ka]
[0051] wherein M is a monovalent cation selected from the group consisting of Li, Na, Ca, K, Zn, and Mg. It may contain repeat units of the formula:
[0052] Sulfonated polyesters are linear, amorphous polyesters that can typically be dispersed in polar media such as water without the aid of surfactants or other hydrophilic species such as amines. This polar media dispersibility can be attributed to the ionic nature of the sulfonate substituents attached to the polymer chain. Examples of sulfonated polyesters can also aid in the dispersion of hydrophobic raw materials in aqueous media.
[0053] Exemplary sulfonated polyesters that may be useful according to the present invention may be prepared from monomer residues including dicarboxylic acid monomer residues, sulfomonomer residues, and diol monomer residues. The sulfomonomer may be a dicarboxylic acid, a diol, or a hydroxycarboxylic acid. Thus, the term "monomer residue" as used herein means a residue of a dicarboxylic acid, a diol, or a hydroxycarboxylic acid. "Repeating unit" or "repeat unit" as used herein means an organic structure having two monomer residues linked through a carbonyloxy group. The sulfonated polyesters of the present invention may contain approximately equal molar ratios of acid residues (100 mol%) and diol residues (100 mol%), which react in approximately equal proportions such that the total number of moles of repeat units equals 100 mol%.
[0054] In one embodiment, or in combination with any of the mentioned embodiments, the sulfomonomer residue comprises a salt of a sulfoisophthalate moiety derived, for example, from sodium sulfoisophthalate (5-SSIPA), 5-sodiisodimethylsulfoisophthalate, or esters thereof. The sulfoisophthalate moiety can also be derived from other metal sulfoisophthalates and their esters. For example, the relevant metal M below can be a monovalent cation such as Na+, Li+, or K+.
[0055] [ka]
[0056] Salts of sulfoisophthalate moieties. In addition to sulfoisophthalate moieties, the sulfonated polymer may contain one or more residues of glycol monomers, dicarboxylic acid monomers, and / or diamine monomers. Examples of sulfonated polymers include sulfonated polyesters, sulfopolyamides, and sulfonated polyesteramides.
[0057] In one embodiment, or in combination with any of the mentioned embodiments, the sulfonated polyesters described herein have the following structural formula:
[0058] [ka]
[0059] wherein A is a dicarboxylic acid repeat unit and G is a glycol repeat unit. Examples of dicarboxylic acid repeat units A include, but are not limited to, terephthalic acid, isophthalic acid, and / or 1,4-cyclohexanedicarboxylic acid (1,4-CHDA). Examples of glycol repeat units G include, but are not limited to, ethylene glycol (EG), diethylene glycol (DEG), triethylene glycol (TEG), neopentyl glycol (NPG), and / or 1,4-cyclohexanedimethanol (CHDM) and tetramethylcyclobutanediol (TMCD). The following are exemplary monomeric residues:
[0060] [ka]
[0061] In one embodiment, or in combination with any of the mentioned embodiments, the sulfonated polymer or sulfonated polyester can be a linear polymer having an average molecular weight (MW) of at least 2 kDaltons (Da). In one embodiment, or in combination with any of the mentioned embodiments, the sulfonated polymer or sulfonated polyester can have an average MW of 2-15 kDa, 4-15 kDa, 5-15 kDa, 5-12 kDa, or 7-10 kDa.
[0062] In one or more embodiments, the sulfonated polyesters described herein may have an intrinsic viscosity, hereinafter abbreviated as "Ih.V", of at least 0.1 dL / g, e.g., at least 0.2, at least 0.3 dL / g, or at least 0.4 dL / g, and up to 0.5 dL / g, measured in a 60 / 40 parts by weight solution of phenol / tetrachloroethane solvent at 20° C. and at a concentration of 0.5 g of sulfonated polyester in 100 mL of solvent. In one or more embodiments, the sulfonated polyesters described herein may have an intrinsic viscosity of 0.10 to 0.60 dL / g, measured in a 60 / 40 parts by weight solution of phenol / tetrachloroethane solvent at 20° C. and at a concentration of 0.5 g of sulfonated polyester in 100 mL of solvent.
[0063] Exemplary sulfonated polyesters have a glass transition temperature, Tg, of -60 to 60°C. The glass transition temperature (Tg) is the temperature at which a glassy polymer becomes molten / rubbery when heated and vice versa when cooled. In various embodiments, the sulfonated polyesters can have a glass transition temperature, Tg, ranging from 30°C to 120°C; 30°C to 100°C; 40°C to 90°C; 40°C to 80°C; 50°C to 70°C; 35°C to 65°C; 40°C to 60°C; 35°C to 55°C; 40°C to 50°C; 45°C to 60°C; 35°C to 45°C; 50°C to 65°C; 50°C to 55°C; 35°C to 40°C; 45°C to 50°C; or 55°C to 65°C. In some embodiments, the sulfonated polyester may have a Tg greater than 35°C, greater than 40°C, greater than 45°C, greater than 50°C, or greater than 55°C, or less than 60°C, less than 55°C, less than 50°C, less than 45°C, or less than 40°C.
[0064] The mole percentages provided in this disclosure can be based on the total moles of acid residues, the total moles of diol residues, or the total moles of repeat units. For example, a sulfonated polyester containing 30 mole % of sulfomonomers, which can be dicarboxylic acids, diols, or hydroxycarboxylic acids, based on the total repeat units, means that there are 30 moles of sulfomonomer residues for every 100 moles of repeat units. Similarly, a sulfonated polyester containing 30 mole % of dicarboxylic acid sulfomonomers, including sulfoisophthalic acid moieties, based on the total acid residues, means that the sulfonated polyester contains 30 moles of sulfomonomer residues for every 100 moles of acid residues.
[0065] The term "polyester", as used herein, encompasses both "homopolyesters" and "copolyesters" and refers to synthetic polymers prepared by polycondensation of difunctional carboxylic acids with difunctional hydroxyl compounds. As used herein, the term "sulfonated polyester" refers to any polyester containing a sulfomonomer containing a sulfoisophthalic acid moiety. Typically, the difunctional carboxylic acid is a dicarboxylic acid and the difunctional hydroxyl compound is a dihydric alcohol, such as glycols and diols. Alternatively, the sulfonated polyester may contain a hydroxy acid monomer, such as p-hydroxybenzoic acid, and the difunctional hydroxyl compound may be an aromatic nucleus with two hydroxy substituents, such as hydroquinone. The term "residue", as used herein, refers to any organic structure incorporated into a polymer through a polycondensation reaction associated with the corresponding monomer. Thus, the dicarboxylic acid residue may be derived from a dicarboxylic acid monomer or its associated acid halide, ester, salt, anhydride, or mixtures thereof. Thus, as used herein, the term dicarboxylic acid is intended to include any derivative of a dicarboxylic acid, including dicarboxylic acids and their associated acid halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides, or mixtures thereof, that are useful in the polycondensation process with diols to make high molecular weight polyesters.
[0066] The sulfonated polyesters of the present disclosure include one or more dicarboxylic acid residues. Depending on the type and concentration of the sulfomonomer, the dicarboxylic acid residues may comprise 60 mol% to 100 mol% of the acid residues. Other examples of concentration ranges of the dicarboxylic acid residues are 60 mol% to 95 mol%, and 70 mol% to 95 mol%. Examples of dicarboxylic acids that may be used include aliphatic dicarboxylic acids, cycloaliphatic dicarboxylic acids, aromatic dicarboxylic acids, or mixtures of two or more of these acids. Thus, suitable dicarboxylic acids include succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, itaconic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, diglycolic acid, 2,5-norbornanedicarboxylic acid, phthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, diphenic acid, 4,4'-oxydibenzoic acid, 4,4'-sulfonyldibenzoic acid, and isophthalic acid. Examples of dicarboxylic acid residues are isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid, or, when diesters are used, dimethyl terephthalate, dimethyl isophthalate, and dimethyl-1,4-cyclohexanedicarboxylate, with isophthalic acid and terephthalic acid residues being illustrative. Dicarboxylic acid methyl esters are a specific example embodiment; it is also acceptable to include higher alkyl esters such as ethyl, propyl, isopropyl, butyl, etc. Additionally, aromatic esters, particularly phenyl, may also be utilized.
[0067] The sulfonated polyesters include from 4 mol % to 40 mol %, based on the total repeat units, of the residues of at least one sulfomonomer having two functional groups and one or more sulfonate groups attached to an aromatic or alicyclic ring, where the functional groups are hydroxyl, carboxyl, or a combination thereof. Additional examples of concentration ranges for the sulfomonomer residues are from 4 mol % to 35 mol %, from 8 mol % to 30 mol %, and from 8 mol % to 25 mol %, based on the total repeat units. The sulfomonomer may be a dicarboxylic acid or ester thereof containing a sulfonate group, a diol containing a sulfonate group, or a hydroxy acid containing a sulfonate group. The term "sulfonate" refers to the structure "-SO 3 " and the term "sulfonate" refers to the anion of a sulfonic acid having the structure "-SO 3 The sulfonic acid salt has a sulfonic acid salt with a group M, where M is the sulfonate cation. The sulfonate cation can be a metal ion such as Li+, Na+, K+, etc. Alternatively, the sulfonate cation can be a non-metallic, such as a nitrogen base, as described, for example, in U.S. Pat. No. 4,304,901. The nitrogen-based cation is derived from a nitrogen-containing base, which can be an aliphatic, cycloaliphatic, or aromatic compound. Examples of such nitrogen-containing bases include ammonia, dimethylethanolamine, diethanolamine, triethanolamine, pyridine, morpholine, and piperidine. Since monomers containing nitrogen-based sulfonates are typically not thermally stable at the conditions required to bring the polymer to a molten state, the method of the present disclosure for preparing a sulfonated polyester containing nitrogen-based sulfonate groups is to disperse, dissipate, or dissolve the required amount of a polymer containing sulfonate groups in water in the form of its alkali metal salt, and then exchange the alkali metal cation for the nitrogen-based cation.
[0068] Examples of sulfomonomer residues include monomer residues in which the sulfonate group is attached to an aromatic or alicyclic dicarboxylic acid or residue thereof, such as dicarboxylic acids or residues derived from benzene, naphthalene, diphenyl, oxydiphenyl, sulfonyldiphenyl, and methylenediphenyl, or alicyclic rings such as cyclohexyl, cyclopentyl, cyclobutyl, cycloheptyl, and cyclooctyl. Other examples of sulfomonomer residues that may be used in the present disclosure are metal sulfonates of sulfophthalic acid, sulfoterephthalic acid, sulfoisophthalic acid, or combinations thereof. Other examples of sulfomonomers that may be used can be 5-sodiosulfoisophthalic acid and its esters. When the sulfomonomer residue is derived from 5-sodiosulfoisophthalic acid, typical sulfomonomer concentration ranges are 4 mol% to 35 mol%, 8 mol% to 30 mol%, and about 8 mol% to 25 mol%, based on the total moles of acid residues.
[0069] The sulfomonomers used in the preparation of sulfonated polyesters are known compounds and can be prepared using methods well known in the art.For example, sulfomonomers in which the sulfonate group is attached to an aromatic ring can be prepared by sulfonating an aromatic compound with pyrosulfuric acid to obtain the corresponding sulfonic acid, which is then reacted with a metal oxide or base, such as sodium acetate, to prepare the sulfonate salt.The preparation procedures for various sulfomonomers are described, for example, in U.S. Pat. Nos. 3,779,993; 3,018,272; and 3,528,947.
[0070] If the polymer is in dispersed form, it is also possible to prepare sulfonated polyesters using, for example, an ion exchange method using a sulfonic acid sodium salt and replacing the sodium with a different ion such as zinc. Inasmuch as the sodium salt is typically more soluble in the polymer reactant melt phase, this type of ion exchange procedure is generally superior to preparing the polymer with a divalent salt.
[0071] The sulfonated polyesters include one or more diol residues which may include aliphatic, cycloaliphatic, and / or aralkyl glycols. Examples include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, and polyalkylene glycols. Other suitable glycols include cycloaliphatic glycols having 6 to 20 carbon atoms and aliphatic glycols having 3 to 20 carbon atoms. Specific examples of such glycols are ethylene glycol, propylene glycol, 1,3-propanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2,2-dimethyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethanol, 2,2,4-trimethyl-1,6-hexanediolthiodiethanol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and p-xylylenediol. The sulfonated polyesters may also comprise mixtures of glycols.
[0072] Diols also include polyfunctional alcohols (polyols). Examples of polyols include neopentyl glycol; butylene glycol; 1,4-butanediol, hexylene glycol; 1,6-hexanediol; polyglycols such as diethylene glycol or triethylene glycol; triols such as glycerin, trimethylolethane, trimethylolpropane; and other higher functional alcohols such as pentaerythritol, sorbitol, mannitol, and the like. Diol residues have the structure H-(OCH 2 -CH 2 )n-OH and may contain 25 mol % to 100 mol %, based on the total diol residues, of residues of poly(ethylene glycol) having the formula: where n is an integer ranging from 2 to 500. Non-limiting examples of lower molecular weight polyethylene glycols, for example, where n is 2 to 6, are diethylene glycol, triethylene glycol, and tetraethylene glycol. Of these lower molecular weight glycols, diethylene glycol and triethylene glycol are representative. Higher molecular weight polyethylene glycols (abbreviated herein as "PEG"), where n is 7 to 500, include, but are not limited to, the commercially available products known under the name CARBOWAX®, a product of Dow Chemical Company (formerly Union Carbide). Typically, PEG is used in combination with other diols, such as, for example, diethylene glycol or ethylene glycol. Based on values of n ranging from greater than 7 to 500, the molecular weight can range from greater than 300 to 22,000 g / mol. Molecular weight and mole % are inversely proportional to each other; specifically, as the molecular weight increases, the mole % decreases to achieve a given degree of hydrophilicity. Illustrating this concept is the consideration that, for example, PEG having a molecular weight of 1000 g / mol may constitute up to 10 mol % of the total diols, while PEG having a molecular weight of 10,000 g / mol may typically be incorporated at a level of less than 1 mol % of the total diols.
[0073] Certain dimer, trimer, and tetramer diols may be formed in situ due to side reactions that can be controlled by changing process conditions. For example, various amounts of diethylene, triethylene, and tetraethylene glycols may be formed from ethylene glycol by acid-catalyzed dehydration reactions that occur easily when the polycondensation reaction is carried out under acidic conditions. The presence of buffer solutions is well known to those skilled in the art and may be added to the reaction mixture to retard the progression of these side reactions. However, additional compositional allowances are possible when the buffer is omitted and the dimerization, trimerization, and tetramerization reactions are allowed to proceed.
[0074] The sulfonated polyesters of the present disclosure may contain 0 mol% to 25 mol% of residues of branching monomers having three or more functional groups, based on the total repeat units, where the functional groups are hydroxyl, carboxyl, or combinations thereof. Non-limiting examples of branching monomers are 1,1,1-trimethylolpropane, 1,1,1-trimethylolethane, glycerin, pentaerythritol, erythritol, threitol, dipentaerythritol, sorbitol, trimellitic anhydride, pyromellitic dianhydride, dimethylolpropionic acid, or combinations thereof. Further examples of branching monomer concentration ranges are 0 mol% to 20 mol% and 0 mol% to 10 mol%. The presence of branching monomers may provide many possible benefits to the sulfonated polyesters of the present disclosure, such as the ability to tailor rheology, solubility, and tensile properties. For example, at a given molecular weight, branched sulfonated polyesters also have a greater concentration of end groups that may facilitate crosslinking reactions after polymerization compared to their linear analogs. However, at high concentrations of branching agent, the sulfonated polyesters can be prone to gelation.
[0075] The chemical structures of exemplary sulfonated polyesters are provided below.
[0076] [ka]
[0077] Examples of commercially available sulfonated polyesters suitable for the present invention include Eastman AQ™ 55S polymer and Eastman AQ™ 38S polymer, available from Eastman Chemical Company (Kingsport, Tennessee). Eastman AQ™ 55S polymer has, on average, the following properties: glass transition temperature of 51-55° C., intrinsic viscosity of 0.29-0.37 dL / g, acid number of less than 2 mg KOH / g, hydroxyl number of less than 10 mg KOH / g, and bulk density of 814.8 kg / m3 (6.8 lbs / gal). Eastman AQ™ 38S polymer has, on average, the following properties: glass transition temperature of 35-38° C., intrinsic viscosity of 0.32-0.40 dL / g, acid number less than 2 mg KOH / g, hydroxyl number less than 10 mg KOH / g, and bulk density of 778.9 kg / m3 (6.5 lbs / gal).
[0078] Other suitable sulfonated polyesters are also contemplated.For example, suitable sulfonated polyesters are disclosed and described in U.S. Patent Nos. 8,580,872; 7,923,526; 5,369,211; 6,171,685; 7,902,094; 6,162,890; and U.S. Patent Application Publication No. 2014 / 0357789, the contents and disclosures of each of which are incorporated herein by reference.
[0079] In one or more embodiments, the melt-processable plasticized cellulose ester composition of the present invention may contain one or more optional additives.Non-limiting examples of additives include UV absorbers, antioxidants, acid scavengers such as epoxidized soybean oil, radical scavengers, epoxidized oils and their fillers, additives, biopolymers, stabilizers, and / or odor control waxes, compatibilizers, biodegradation accelerators, dyes, pigments, colorants, gloss regulators, lubricants, antioxidants, viscosity regulators, antifungal agents, antifog agents, heat stabilizers, impact regulators, antibacterial agents, softeners, processing aids, mold release agents, and combinations thereof.It should be noted that the same type of compound or material may be identified as or included in multiple categories of components in melt-processable plasticized cellulose ester composition. For example, polyethylene glycol (PEG) can function as a plasticizer or as an additive that does not function as a plasticizer, such as a hydrophilic polymer or biodegradation promoter, where lower molecular weight PEGs have a plasticizing effect and higher molecular weight PEGs function as hydrophilic polymers but without a plasticizing effect.
[0080] In an embodiment, the melt-processable plasticized cellulose ester composition comprises at least one filler. In an embodiment, the filler is of a type and present in an amount that enhances the biodegradability and / or compostability of the article that comprises the composition and is prepared or formed from the composition. In an embodiment, the melt-processable plasticized cellulose ester composition comprises at least one filler selected from: carbohydrates (sugars and salts), cellulosic and organic fillers (wood flour, wood fiber, hemp, cellulose carbon, coal particles, graphite, and starch), mineral and inorganic fillers (calcium carbonate, talc, silica, titanium dioxide, glass fiber, glass spheres, boronitride, aluminum trihydrate, magnesium hydroxide, calcium hydroxide, alumina, and clay), food waste or by-products (eggshell, distillers grains, and coffee grounds), desiccants (e.g. calcium sulfate, magnesium sulfate, magnesium oxide, calcium oxide), or combinations (e.g., mixtures) thereof. In an embodiment, the melt-processable plasticized cellulose ester composition comprises at least one filler that also functions as a color additive. In an embodiment, the color additive filler can be selected from: carbon, graphite, titanium dioxide, opacifiers, dyes, pigments, toners, and combinations thereof. In an embodiment, the melt-processable plasticized cellulose ester composition comprises at least one filler that also functions as a stabilizer or flame retardant.
[0081] In an embodiment, the melt-processable plasticized cellulose ester composition may optionally further comprise a biodegradable polymer (other than cellulose acetate). In an embodiment, the other biodegradable polymer may be selected from polyhydroxyalkanoates (PHA and PHB), polylactic acid (PLA), polycaprolactone polymers (PCL), polybutylene adipate terephthalate (PBAT), polyethylene succinate (PES), polyvinyl acetate (PVA), polybutylene succinate (PBS) and copolymers (such as polybutylene succinate-co-adipate (PBSA)), cellulose esters, cellulose ethers, starches, proteins, derivatives thereof, and combinations thereof. In an embodiment, the melt-processable plasticized cellulose ester composition may comprise two or more biodegradable polymers. In embodiments, the biodegradable polymer (other than cellulose acetate) is present in an amount of 0.1 to less than 50 wt%, or 1 to 40 wt%, or 1 to 30 wt%, or 1 to 25 wt%, or 1 to 20 wt%, based on the total weight of the melt-processible plasticized cellulose ester composition. In embodiments, the melt-processible plasticized cellulose ester composition contains the biodegradable polymer (other than cellulose acetate) in an amount of 0.1 to less than 50 wt%, or 1 to 40 wt%, or 1 to 30 wt%, or 1 to 25 wt%, or 1 to 20 wt%, based on the total weight of the cellulose ester plus the biodegradable polymer. In embodiments, the biodegradable polymer has a molecular weight of 10,000 to 1,000,000, or 50,000 to 1,000,000, or 100,000 to 1,000,000, or 250,000 to 1,000,000, or 500,000 to 1,000,000, as measured using gel permeation chromatography (GPC) with a refractive index detector and polystyrene standards utilizing a solvent of methylene chloride. The PHAs include those having a weight average molecular weight (Mw) in the range of 00 to 1,000,000, or 600,000 to 1,000,000, or 600,000 to 900,000, or 700,000 to 800,000, or 10,000 to 500,000, or 10,000 to 250,000, or 10,000 to 100,000, or 10,000 to 50,000.In embodiments, the PHA may include polyhydroxybutyrate-co-hydroxyhexanoate.
[0082] In certain embodiments, melt-processable plasticized cellulose ester composition optionally comprises at least one stabilizer.In general, it may be desirable for melt-processable plasticized cellulose ester composition and the article that comprises or is formed from or prepared using them to be compostable and / or biodegradable, but a certain amount of stabilizer can be added to provide a selected shelf life or stability against, for example, light exposure, oxidation stability, or hydrolysis stability.In various embodiments, stabilizer can include UV absorbers, antioxidants (such as ascorbic acid, BHT, BHA), other acids and radical scavengers, epoxidized oils, such as epoxidized soybean oil, or combinations thereof.
[0083] Antioxidants (AOs) can be divided into several classes, including primary antioxidants and secondary antioxidants. Primary antioxidants are generally known to function essentially as free radical terminating agents (scavengers). Secondary antioxidants are generally known to dissociate hydroperoxides (ROOH) into non-reactive products before they dissociate into alkoxy and hydroxyl radicals. Secondary antioxidants are often used in combination with free radical scavengers (primary antioxidants) to achieve a synergistic inhibitory effect, and secondary AOs are used to extend the life of phenolic-type primary AOs.
[0084] "Primary antioxidants" are antioxidants that act by reacting with peroxide radicals via hydrogen transfer, quenching the radicals. Primary antioxidants generally contain reactive hydroxy or amino groups, such as in sterically hindered phenols and secondary aromatic amines. Examples of primary antioxidants are BHT, Irganox™ 1010, 1076, 1726, 245, 1098, 259, and 1425; Ethanox™ 310, 376, 314, and 330; Evernox™ 10, 76, 1335, 1330, 3114, MD 1024, 1098, 1726, 120.2246, and 565; Anox™ 20, 29, 330, 70, IC-14, and 1315; Lowinox™ 520, 1790, 22IB46, 22M46, 44B25, AH25, GP45, cellulose acetate 22, CPL, 3 Includes HD98, TBM-6, and WSP; Naugard™ 431, PS48, SP, and 445; Songnox™ 1010, 1024, 1035, 1076 CP, 1135LQ, 1290PW, 1330FF, 1330PW, 2590PW, and 3114FF; and ADK Stab AO-20, AO-30, AO-40, AO-50, AO-60, AO-80, and AO-330.
[0085] "Secondary antioxidants" are often hydroperoxide dissociators. Hydroperoxide dissociators act by reacting with hydroperoxides and dissociating them into non-radical, non-reactive and thermally stable products. They are often used in conjunction with primary antioxidants. Examples of secondary antioxidants include organophosphorus (e.g., phosphites, phosphonites) and organosulfur compounds. The phosphorus and sulfur atoms of these compounds react with peroxides to convert them to alcohols. Examples of secondary antioxidants are Ultranox 626, Ethanox™ 368, 326, and 327; Doverphos™ LPG11, LPG12, DP S-680, 4, 10, S480, S-9228, S-9228T; Evernox™ 168 and 626; Irgafos™ 126 and 168; Weston™ DPDP, DPP, EHDP, PDDP, TDP, TLP, and TPP; Mark™ CH302, CH55, TNPP, CH66, CH300, CH301, CH302, CH304, and CH305; ADK Stab2112, HP-10, PEP-8, PEP-36, 1178, 135A, 1500, 3010, C, and TPP; Weston 439, DHOP, DPDP, DPP, DPTDP, EHDP, PDDP, PNPG, PTP, PTP, TDP, TLP, TPP, 398, 399, 430, 705, 705T, TLTTP, and TNPP; Alkanox 240, 626, 626A, 627AV, 618F, and 619F; and Songnox™ 1680FF, 1680PW, and 6280FF.
[0086] In an embodiment, the melt-processable plasticized cellulose ester composition comprises at least one stabilizer, the stabilizer comprising one or more secondary antioxidants. In an embodiment, the stabilizer comprises a first stabilizer component selected from one or more secondary antioxidants, and a second stabilizer component selected from one or more primary antioxidants, citric acid, or a combination thereof.
[0087] In embodiments, the stabilizer comprises one or more secondary antioxidants in an amount, in weight percent, ranging from 0.01 to 0.8, or 0.01 to 0.7, or 0.01 to 0.5, or 0.01 to 0.4, or 0.01 to 0.3, or 0.01 to 0.25, or 0.01 to 0.2, or 0.05 to 0.8, or 0.05 to 0.7, or 0.05 to 0.5, or 0.05 to 0.4, or 0.05 to 0.3, or 0.05 to 0.25, or 0.05 to 0.2, or 0.08 to 0.8, or 0.08 to 0.7, or 0.08 to 0.5, or 0.08 to 0.4, or 0.08 to 0.3, or 0.08 to 0.25, or 0.08 to 0.2, based on the total weight of the composition. In one class of this embodiment, the stabilizer comprises a secondary antioxidant that is a phosphite compound.In one class of this embodiment, the stabilizer comprises a secondary antioxidant that is a phosphite compound and another secondary antioxidant that is DLTDP.
[0088] In a subclass of this class, the stabilizer further comprises a second stabilizer component comprising one or more primary antioxidants in an amount ranging from 0.05 to 0.7, or 0.05 to 0.6, or 0.05 to 0.5, or 0.05 to 0.4, or 0.05 to 0.3, or 0.1 to 0.6, or 0.1 to 0.5, or 0.1 to 0.4, or 0.1 to 0.3, based on the total weight of the composition. In a subclass of this class, the stabilizer further comprises a second stabilizer component comprising citric acid in an amount ranging from 0.05 to 0.2, or 0.05 to 0.15, or 0.05 to 0.1, based on the total weight of the composition. In a subclass of this class, the stabilizer further comprises a second stabilizer component comprising one or more primary antioxidants and citric acid in the amounts disclosed herein. In a subclass of this class, the stabilizer contains less than 0.1 wt.% or no primary antioxidant, based on the total weight of the composition. In a subclass of this class, the stabilizer contains less than 0.05 wt.% or no primary antioxidant, based on the total weight of the composition.
[0089] In embodiments, depending on the application, for example, for disposable food contact applications, the melt-processable plasticized cellulose ester composition may include at least one odor control additive. In embodiments, depending on the application and the ingredients used in the melt-processable plasticized cellulose ester composition, suitable odor control additives may be selected from: vanillin, Pennyroyal M-1178, almond, cinnamyl, spices, spice extracts, volatile organic compounds or small molecules, and Plastidor. In one embodiment, the odor control additive may be vanillin. In embodiments, the melt-processable plasticized cellulose ester composition may include the odor control additive in an amount of 0.01 to 1 wt%, or 0.1 to 0.5 wt%, or 0.1 to 0.25 wt%, or 0.1 to 0.2 wt%, based on the total weight of the composition. The mechanism for the odor control additive may include masking, scavenging, complementation, or a combination thereof.
[0090] As discussed above, the melt-processable plasticized cellulose ester composition may include other optional additives. In an embodiment, the melt-processable plasticized cellulose ester composition may include at least one compatibilizer. In an embodiment, the compatibilizer may be either a non-reactive compatibilizer or a reactive compatibilizer. The compatibilizer may enhance the ability of the cellulose ester or another component to reach a desired small particle size and improve the dispersion of the selected component in the composition. In such an embodiment, depending on the desired formulation, the cellulose ester may be in either the continuous or discontinuous phase of the dispersion. In an embodiment, the compatibilizer used may improve the mechanical and / or physical properties of the composition by modifying the interfacial interaction / bonding between the cellulose ester and another component, such as another biodegradable polymer.
[0091] In embodiments, the melt-processable plasticized cellulose ester composition comprises the compatibilizer in an amount of from about 1 to about 40 wt%, or from about 1 to about 30 wt%, or from about 1 to about 20 wt%, or from about 1 to about 10 wt%, or from about 5 to about 20 wt%, or from about 5 to about 10 wt%, or from about 10 to about 30 wt%, or from about 10 to about 20 wt%, based on the weight of the melt-processable plasticized cellulose ester composition.
[0092] In embodiments, if desired, the melt-processable plasticized cellulose ester composition may include a biodegradation agent and / or dissociation agent, such as, for example, a hydrolysis aid, or any intentional degradation-promoting additive may be added to or contained in the composition, added either during or after the production of cellulose acetate, and melted or solvent blended with cellulose acetate to promote the biodegradability of the melt-processable plasticized cellulose ester composition and / or the compostability and / or disintegrability of articles that contain it or are formed or prepared using it. In embodiments, the additives may promote hydrolysis by releasing acidic or basic residues, and / or accelerate photo (UV) or oxidative degradation, and / or promote the growth of selective microbial colonies in compost and soil media to aid in disintegration and biodegradation. In addition to promoting degradation, these additives may have additional functions, such as improving the processability of the article or improving the mechanical properties of the desired article.
[0093] An example set of possible dissociation agents includes inorganic carbonates, synthetic carbonates, nepheline syenite, talc, magnesium hydroxide, aluminum hydroxide, diatomaceous earth, natural or synthetic silica, calcined clay, etc. In embodiments, it may be desirable for these additives to be well dispersed in the composition matrix. The additives may be used alone or in combination of two or more.
[0094] Another set of examples of possible dissociating agents are aromatic ketones used as oxidative dissociating agents, including benzophenone, anthraquinone, anthrone, acetylbenzophenone, 4-octylbenzophenone, etc. These aromatic ketones may be used alone or in combination of two or more.
[0095] Other examples include cobalt or magnesium salts, such as aliphatic carboxylic acid (C12-C20) salts of cobalt or magnesium, or transition metal compounds used as oxidizing dissociators, such as cobalt stearate, cobalt oleate, magnesium stearate, and magnesium oleate; or anatase titanium dioxide, or titanium dioxide may be used. Mixed-phase titanium dioxide particles, in which both rutile and anatase crystal structures are present in the same particle, may be used. The particles of the photoactivator may have a relatively large surface area, for example, about 10 to about 300 square meters / g, or 20 to 200 square meters / g, as measured by the BET surface area method. The photoactivator may be added to a plasticizer, if desired. These transition metal compounds may be used alone or in combination of two or more.
[0096] Examples of rare earth compounds that can be used as the oxidizing dissociation agent include rare earths belonging to group 3A of the periodic table and their oxides. Specific examples thereof include cerium (Ce), yttrium (Y), neodymium (Nd), rare earth oxides, hydroxides, rare earth sulfates, rare earth nitrates, rare earth acetates, rare earth chlorides, rare earth carboxylates, etc. More specific examples thereof include cerium oxide, cerium sulfate, ammonium cerium sulfate, ammonium cerium nitrate, cerium acetate, lanthanum nitrate, cerium chloride, cerium nitrate, cerium hydroxide, cerium octylate, lanthanum oxide, yttrium oxide, scandium oxide, etc. These rare earth compounds may be used alone or in combination of two or more kinds.
[0097] In one or more embodiments, the melt-processable plasticized cellulose ester composition includes additives with pro-degradant functions to enhance biodegradability, including transition metal salts or chemical catalysts containing transition metals such as cobalt, manganese, and iron. Suitable transition metal salts include tartrates, stearates, oleates, citrates, and chlorides. The additives may further include a free radical scavenging system and one or more inorganic or organic fillers, such as chalk, talc, silica, wollastonite, starch, cotton, recycled cardboard, and plant-derived materials. The additives may also include enzymes, bacterial cultures, swelling agents, CMC, sugars, or other energy sources. The additives may also include hydroxylamine esters and thio compounds.
[0098] In certain embodiments, other possible biodegradation and / or dissociation agents may include swelling agents and disintegration agents. Swelling agents may be hydrophilic materials that increase in volume after absorbing water and exert pressure on the surrounding matrix. Disintegration agents may be additives that promote the matrix to break down into smaller pieces in an aqueous environment. Examples include minerals, and polymers, including crosslinked or modified polymers, and swelling hydrogels. In embodiments, the composition may include water-swelling minerals or clays, such as laponite and bentonite, and their salts; hydrophilic polymers, such as poly(acrylic acid) and salts, poly(acrylamide), poly(ethylene glycol), and poly(vinyl alcohol); polysaccharides and gums, such as starch, alginate, pectin, chitosan, psyllium, xanthan gum; guar gum, locust bean gum; and modified polymers, such as crosslinked PVP, sodium starch glycolate, carboxymethylcellulose, gelatinous starch, sodium croscarmellose; or a combination of these additives.
[0099] In embodiments, the melt-processable plasticized cellulose ester composition may include a pH-basic additive that can increase the dissociation or decomposition of the composition or article made or prepared using the melt-processable plasticized cellulose ester composition. Examples of pH-basic additives that can be used as oxidative dissociation agents include alkaline earth metal oxides, alkaline earth metal hydroxides, alkaline earth metal carbonates, alkali metal carbonates, alkali metal bicarbonates, ZnO, and basic Al 2 O 3 In an embodiment, the at least one basic additive is selected from the group consisting of MgO, Mg(OH) 2 , MgCO 3 , CaO, Ca(OH) 2 , CaCO 3 , NaHCO 3 , Na 2 CO 3 , K 2 CO 3 , ZnO KHCO 3 or basic Al 2 O 3 In one embodiment, the alkaline earth metal oxide, ZnO and basic Al 2 O 3 may be used as a basic additive. In embodiments, a combination of different pH-basic additives or a combination of pH-basic additives with other additives may be used. In embodiments, the pH-basic additive has a pH in the range of greater than 7.0 to 10.0, or 7.1-9.5, or 7.1-9.0, or 7.1-8.5, or 7.1-8.0, measured in a 1 wt % water mixture / solution.
[0100] Examples of organic acid additives that may be used as oxidative dissociation agents include acetic acid, propionic acid, butyric acid, valeric acid, citric acid, tartaric acid, oxalic acid, malic acid, benzoic acid, formate, acetate, propionate, butyrate, valerate, citrate, tartarate, oxalate, malate, maleic acid, maleate, phthalic acid, phthalate, benzoate, and combinations thereof.
[0101] Examples of other hydrophilic polymers or biodegradation-promoting agents may include glycols, polyglycols, polyethers, and polyalcohols or other biodegradable polymers, such as poly(glycolic acid), poly(lactic acid), polyethylene glycols, polypropylene glycols, polydioxanes, polyoxalates, poly(a-esters), polycarbonates, polyanhydrides, polyacetals, polycaprolactones, poly(orthoesters), polyamino acids, aliphatic polyesters such as poly(butylene)succinic acid, poly(ethylene)succinic acid, starch, regenerated cellulose, or aliphatic-aromatic polyesters such as PBAT.
[0102] In embodiments, examples of colorants include carbon black, iron oxides, such as red iron oxide or blue iron oxide, titanium dioxide, silicon dioxide, red cadmium, calcium carbonate, kaolin clay, aluminum hydroxide, barium sulfate, zinc oxide, aluminum oxide; and organic pigments, such as azo and diazo and triazo pigments, condensed azo, azo lakes, naphthol pigments, anthrapyrimidines, benzimidazolones, carbazoles, diketopyrrolopyrroles, flavanthrones, indigoid pigments, isoindolinones, isoindolines, isoviolanthrones, metal complex pigments, oxadienes, In certain embodiments, the pigments may include those of the phthalocyanine series, particularly copper phthalocyanine and its nuclear halogenated derivatives, and also lakes of acid, basic and mordant dyes, and isoindolinone pigments, as well as vegetable and vegetable dyes, and other available colorants or dyes.
[0103] In embodiments, sheen modifiers and fillers for adjusting the surface gloss may include silica, talc, clay, barium sulfate, barium carbonate, calcium sulfate, calcium carbonate, magnesium carbonate, and the like.
[0104] Suitable flame retardants may include silica, metal oxides, phosphates, catechol phosphates, resorcinol phosphates, borates, inorganic hydrates, and aromatic polyhalides.
[0105] While it is desirable for articles comprising and formed or prepared using the melt-processible plasticized cellulose ester compositions to be compostable, disintegratable and / or biodegradable, certain amounts of antifungal, antibacterial, or antimicrobial agents may be added to provide a selected shelf life, useful service life, or stability.Such agents include polyene antifungals (e.g., natamycin, rimocidin, filipin, nystatin, amphotericin B, kajicin, and hamycin), imidazole antifungals such as miconazole (available as MICELLULOSE ACETATETIN™ from WellSpring Pharmaceutical Corporation), ketoconazole (commercially available as NIZORAL® from McNeil consumer Healthcare), clotrimazole (available as LOTRAMIN® and LOTRAMIN® from Merck), and the like. AF® and available from Bayer as CASTEN®), econazole, omoconazole, bifonazole, butoconazole, fenticonazole, isoconazole, oxiconazole, sertaconazole (commercially available as ERTACZO® from OrthoDematologics), sulconazole, and tioconazole; triazole antifungals such as fluconazole, itraconazole, isavuconazole, ravuconazole, posaconazole, voriconazole, terconazole, and albaconazole, thiazole antifungals (e.g., abafungin), allylamine antifungals (e.g., terbinafine (commercially available as LAMISIL® from Novartis Consumer Health, Inc.), naftifine (commercially available as NAFTIN® from Merz Pharmaceuticals), and butenafine (commercially available as LOTRAMIN® from Merck), ULTRA®), echinocandin antifungals (e.g., anidulafungin, capofungin, and micafungin), polygodial, benzoic acid, ciclopirox, tolnaftate (e.g., available from MDS Consumer Care, Inc. as TINACTIN®), undecylenic acid, flucytosine, 5-fluorocytosine, griseofulvin, haloprogin, caprylic acid, and any combination thereof.
[0106] Viscosity modifiers having the purpose of modifying the melt flow index or viscosity of the melt-processible plasticized cellulose ester composition that may be used include polyethylene and polypropylene glycols, and glycerin.
[0107] In embodiments, other components that may be included in the composition may function as release or lubricants (e.g., fatty acids, ethylene glycol distearate), antiblock or slip agents (e.g., one or more fatty acid esters, metal stearates (e.g., zinc stearate), and waxes), antifog agents (e.g., surfactants), heat stabilizers (e.g., epoxy stabilizers, derivatives of epoxidized soybean oil (ESBO), linseed oil, and sunflower oil), antistatic agents, foaming agents, biocides, impact modifiers, or reinforcing fibers. More than one component may be present in the composition. It is noted that additional components may perform more than one function in the composition. The different (or specific) functionality of any particular additive (or component) to the composition may depend on its physical properties (e.g., molecular weight, solubility, melting temperature, Tg, etc.) and / or the amount of such additive / component in the overall composition. For example, polyethylene glycol may function as a plasticizer at one molecular weight, or as a hydrophilic agent (having little or no plasticizing effect) at another molecular weight.
[0108] In embodiments, flavorings may be added if desired. Examples of flavorings include spices, spice extracts, herb extracts, essential oils, aromatic salts, volatile organic compounds, volatile small molecules, methyl formate, methyl acetate, methyl butyrate, ethyl acetate, ethyl butyrate, isoamyl acetate, pentyl butyrate, pentyl pentanoate, octyl acetate, myrcene, geraniol, nerol, citral, citronellal, citronellol, linalool, nerolidol, limonene, camphor, terpineol, alpha-ionone, thujone, benzaldehyde, eugenol, isoeugenol, cinnamaldehyde, ethyl maltol, vanilla. , vanillin, cinnamyl alcohol, anisole, anethole, estragole, thymol, furaneol, methanol, rosemary, lavender, citrus, freesia, apricot flower, green, peach, jasmine, rosewood, pine, thyme, hornwort, musk, vetiver, myrrh, blackcurrant, bergamot, grapefruit, acacia, passionflower, sandalwood, tonka bean, mandarin, neroli, violet leaves, gardenia, red fruits, ylang-ylang, goldenrod, mimosa, tonka bean, wood, ambergris Squirrel, daffodil, hyacinth, narcissus, blackcurrant bud, iris, raspberry, lily of the valley, sandalwood, vetiver, cedarwood, neroli, strawberry, carnation, oregano, honey, civet, heliotrope, caramel, coumarin, patchouli, dewberry, heronial, coriander, pimento berry, labdanum, cassi, aldehyde, orchid, amber, iris, tuberose, palmarosa, cinnamon, nutmeg, moss, snowbell, pineapple, foxglove, tulip, wisteria, clematis, Ambergris, gum, resin, civet, plum, castoreum, civet, myrrh, geranium, rose violet, jonquil, spicy carnation, galbanum, petitgrain, iris, honeysuckle, pepper, raspberry, benzoin, mango, coconut, hesperides, castoreum, osmanthus, mousse de chene, nectarine, mint, anise, cinnamon, iris, apricot, plumeria, marigold, rose otto, daffodil, tolu balsam, frankincense, amber, orange blossom, bourbon vetiver,Opopanax, white musk, papaya, sugar candy, jackfruit, tangerine, lotus flower, lily of the valley, mulberry, absinthe, ginger, juniper, benzoin, peony, violet, lemon, lime, hibiscus, white rum, basil, lavender, balsamic, fortified olive, sweet osmanthus, calocalunde, white orchid, calla lily, white rose, rubrum lily, tagetes, ambergris, ivy, grass, rubber grass, spearmint, clary sage, cottonwood, grape, plumbell, lotus, Cyclamen, Orchid, Glycine, Tahiti Tiare, Ginger Lily, Green Osmanthus, Passion Flower, Blue Rose, Bay Lamium, Cassia, African Tagetes, Anatolian Rose, Auvergne Narcissus, British Bloom, British Bloom Chocolate, Bulgarian Rose, Chinese Patchouli, Chinese Gardenia, Calabrian Mandarin, Comoro Tuberose, Ceylon Cardamom, Caribbean Passion Fruit, Damascena Rose, Georgia Peach, Maidenhair Lily, Egyptian Jasmine , Egyptian marigold, Ethiopian civet, Farnesian cassi, sweet iris, French jasmine, French jonquil, French hyacinth, Guinea orange, Guyana capua, Grasse petitgrain, Grasse rose, Grasse tuberose, Haitian vetiver, Hawaiian pineapple, Israeli basil, Indian sandalwood, Indian Ocean vanilla, Italian bergamot, Italian iris, Jamaican pepper, May rose, Madagascar ylang ylang, Madagascar vanilla, Moroccan jasmine, Moroccan Colossus, Moroccan oakmoss, Moroccan orange blossom, Mysore sandalwood, Oriental rose, Russian leather, Russian coriander, Sicilian mandarin, South African marigold, South American tonka bean, Singaporean patchouli, Spanish orange blossom, Sicilian lime, Reunion Island vetiver, Turkish rose, Thai benzoin, Tunisian orange blossom, Yugoslavian oakmoss, Bernese cedarwood, Utah yarrow, West Indian rosewood, and the like, and any combination thereof.
[0109] As described herein, the melt-processable plasticized cellulose ester composition of the present invention can be melt-processable and useful for forming melt-molded articles. Thus, in another aspect, the present invention is directed to melt-processable cellulose acetate melts. The term "melt" is generally utilized to describe a composition in a flowable, liquid form, sometimes essentially viscous, typically created by raising the composition to a temperature sufficient to promote melt flow (as opposed to, for example, adding a solvent to form a dispersion, suspension or solution). The melt is typically in the form required for melt processing to produce a melt-molded article. In describing a composition as "melt-processable" herein, it is intended to include compositions that can be formed using melt processes such as extrusion, including, but not limited to, profile and sheet extrusion; injection molding; compression molding; blow molding; thermoforming, and the like, that are processable into useful melt-molded articles. Thus, in one or more embodiments, the present invention is directed to cellulose acetate melts that are particularly useful for forming melt-molded articles. In one or more embodiments, the cellulose acetate melt comprises, is prepared from, or is formed from the melt-processable cellulose acetate composition of the present invention. In one or more embodiments, the cellulose ester melt comprises (i) a cellulose ester; (ii) a plasticizer; and (iii) a sulfonated isophthalic acid material.
[0110] An important general feature of the melt processable compositions and melts of the present invention is the unexpected improvement in processability in the manufacture of melt molded articles. One parameter that demonstrates this feature can be melt viscosity. Melt viscosity measures the extrusion rate of a thermoplastic through an orifice at a given temperature and load, and is an important indicator of equipment power consumption, torque and pressure during melt processing. Melt viscosity provides a means of measuring the flow of molten materials and can be used to evaluate the consistency and processability of materials. Representative methods for evaluating processability include melt flow rate (MFR), melt volume flow rate (MVR), using measuring instruments such as capillary rheometers, melt rheology, melt flow index (MFI; described in standards ASTM D1238 and ISO1133), and bar flow evaluation using an injection molding machine. Viscosity is measured according to ASTM D-4440. The formulations described in the present invention have melt viscosities on the order of 3000 poise to 500,000 poise when measured at 230°C and a shear rate of 1 rad / sec. Processing temperatures can be varied to obtain desired flow behavior based on the intended application.
[0111] In one or more embodiments, the melt-processable plasticized cellulose acetate composition of the present invention is a foamable composition.In one or more embodiments, the melt-processable plasticized foamable composition of the present invention comprises: (i) cellulose acetate; (ii) a plasticizer; (iii) a sulfonated isophthalic acid material; (iv) optionally at least one nucleating agent; and (v) at least one foaming agent selected from the group consisting of a physical foaming agent, a chemical foaming agent and a carrier polymer, and combinations thereof.
[0112] In another aspect, the present invention is directed to an article. In one or more embodiments, the article is a melt-formed article. The article of the present invention comprises, is formed from, or is prepared using, a melt-processable plasticized cellulose ester composition comprising a cellulose ester, a plasticizer, and a sulfonated isophthalic acid material. In one or more embodiments, the article can be, for example, an extrusion article, such as a profile extrusion article and a sheet extrusion article; an injection molded article; a compression molded article; a thermoformed article. In one or more embodiments, the melt-formed article of the present invention can be a molded disposable food contact article, including an article that is biodegradable and / or compostable (i.e., any of the industrial or household compostability tests / standards discussed herein). In an embodiment, the melt-processable plasticized cellulose ester composition can be extrudable, moldable, castable, thermoformable, or 3-D printed. "Article" as used herein is defined to include an article in its entirety as well as in its components, elements, or portions thereof that can be joined, bonded, assembled, etc. In an embodiment, the article is environmentally non-sustainable. "Environmentally non-sustainable" is meant to describe a material or article that, upon reaching an advanced level of decay, becomes readily available for total consumption by natural microbial populations. The decomposition of biodegradable cellulose acetate ultimately results in conversion to carbon dioxide, water and biomass.
[0113] In embodiments, articles comprising the melt processable plasticized cellulose ester compositions (discussed herein) have a thickness of 150 mils (3.81 mm), or 140 mils (3.56 mm), or 130 mils (3.30 mm), or 120 mils (3.04 mm), or 110 mils (2.79 mm), or 100 mils (2.54 mm), or 90 mils (2.29 mm), or 80 mils (2.03 mm), or are provided having a maximum thickness of 1.78 mm (70 mils), or 1.52 mm (60 mils), or 1.27 mm (50 mils), or 1.01 mm (40 mils), or 0.76 mm (30 mils), or 0.64 mm (25 mils), or 0.51 mm (20 mils), or 0.38 mm (15 mils), or up to 0.25 mm (10 mils), and may be biodegradable and / or compostable. In embodiments, articles including the melt processable plasticized cellulose ester compositions (discussed herein) are provided having a maximum thickness of up to 150 mils, or 140 mils, or 130 mils, or 120 mils, or 110 mils, or 100 mils, or 90 mils, or 80 mils, or 70 mils, or 60 mils, or 50 mils, or 40 mils, or 30 mils, or 25 mils, or 20 mils, or 15 mils, or 10 mils, and may be environmentally non-sustainable.
[0114] In embodiments, the melt processable plasticized cellulose ester composition of the present invention, as well as the melt and melt molded articles, may contain recycled content.In one or more embodiments, recycled content includes biodegradable cellulose ester regrind.The term "regrind" is intended to include recyclables, scrap, in-house scrap, such as scrap from molders, off-spec or post-industrial source material, which is ground, crushed, crushed, pulverized, etc., to a particle-like or powder-like form.
[0115] In one or more embodiments, the recycled content is provided by a reactant derived from recycled materials, which is a source of one or more acetyl groups on recycled cellulose acetate. In an embodiment, the reactant is derived from recycled plastic. In an embodiment, the reactant is derived from recycled plastic-containing syngas. "Recycled plastic-containing syngas" refers to a syngas obtained from a gas synthesis operation that utilizes a feedstock containing at least some content of recycled plastic, as described more fully in various embodiments herein below. In an embodiment, the recycled plastic-containing syngas can be produced according to any process for producing syngas described herein; can include or consist of any of the syngas compositions or syngas composition streams described herein; or cellulose ester can be produced from any feedstock composition described herein.
[0116] In an embodiment, the feedstock (for the gas synthesis operation) may be in the form of a combination of one or more particulate fossil fuel sources and particulate recycled plastic. In one embodiment, or in any of the embodiments mentioned, the solid fossil fuel source may include coal. In an embodiment, the feedstock is fed into a gasifier along with an oxidant gas, and the feedstock is converted to synthesis gas.
[0117] In an embodiment, recycled plastic-containing syngas is utilized to make at least one chemical intermediate in a reaction scheme to make recycled cellulose ester.In an embodiment, recycled plastic-containing syngas may be a component of feedstock (used to make at least one cellulose acetate intermediate) or a reactant that includes other sources of synthesis gas, hydrogen, carbon monoxide, or combinations thereof.In one embodiment, or in any of the embodiments mentioned, recycled plastic-containing syngas is the only source of synthesis gas used to make cellulose acetate intermediate.
[0118] In embodiments, the cellulose ester intermediates produced using recycled synthesis gas, for example recycled plastic synthesis gas, can be selected from methanol, acetic acid, methyl acetate, acetic anhydride and combinations thereof.In embodiments, the cellulose ester intermediates can be at least one reactant or at least one product in one or more of the following reactions: (1) synthesis gas is converted to methanol; (2) synthesis gas is converted to acetic acid; (3) methanol is converted to acetic acid, for example, methanol is carbonylated to produce acetic acid; (4) methanol and acetic acid are converted to methyl acetate; and (5) methyl acetate is converted to acetic anhydride, for example, methyl acetate and methanol are carbonylated to produce acetic acid and acetic anhydride.
[0119] In an embodiment, the recycled plastic-containing syngas is used to produce at least one cellulose reactant. In an embodiment, the recycled plastic-containing syngas is used to produce at least one recycled cellulose ester.
[0120] In an embodiment, recycled plastic-containing syngas is utilized to make acetic anhydride. In an embodiment, the syngas containing recycled plastic-containing syngas is first converted to methanol, and then this methanol is used in a reaction scheme to make acetic anhydride. "RPS acetic anhydride" refers to acetic anhydride that is derived from recycled plastic-containing syngas. By derived, it is meant that at least some of the feedstock source material (used in any reaction scheme to make cellulose ester intermediate) has some content of recycled plastic-containing syngas.
[0121] In an embodiment, RPS acetic anhydride is utilized as a cellulose acetate intermediate reactant in the esterification of cellulose to prepare recycled cellulose acetate, as discussed more fully above. In an embodiment, RPS acetic acid is utilized as a reactant to prepare cellulose acetate or cellulose diacetate.
[0122] In embodiments, recycled cellulose esters are prepared from a cellulose reactant that includes acetic anhydride derived from recycled plastic-containing syngas. In an embodiment, the recycled plastic-containing syngas comprises a gasification product from a gasification feedstock. In one embodiment, the gasification product is produced by a gasification process using a gasification feedstock comprising recycled plastic. In an embodiment, the gasification feedstock comprises coal.
[0123] In an embodiment, the gasification feedstock comprises a liquid slurry comprising coal and recycled plastics. In an embodiment, the gasification process comprises gasification of said gasification feedstock in the presence of oxygen.
[0124] In one or more embodiments, the melt-processible cellulose acetate composition comprises at least one cellulose ester having at least one substituent on the anhydroglucose unit (AGU) derived from one or more chemical intermediates, at least one of which is derived, at least in part, from recycled plastic-containing syngas.
[0125] In an embodiment, the cellulose ester of the melt-processable plasticized cellulose ester composition comprises the cellulose ester derived from renewable sources, such as the cellulose from wood or cotton linters, and the cellulose acetate derived from recycled material sources, such as recycled plastics or recycled synthetic gas.Therefore, in an embodiment, there is provided a melt-processable plasticized cellulose acetate composition that is biodegradable and contains both renewable and recycled content, i.e., is made from renewable and recycled sources.
[0126] In embodiments, the composition, melt and / or melt-formed article of the present invention may have a degree of decomposition or decomposability. The degree of decomposition may be characterized by the weight loss of the sample over a given period of exposure to a particular environmental condition. In some cellulose esters, the cellulose ester shows at least about 5, 10, 15, or 20 percent weight loss after 60 days of burial in soil, and / or at least about 15, 20, 25, 30, or 35 percent weight loss after 15 days of exposure in a typical municipal composting device. However, the rate of decomposition may vary depending on the particular end use. Exemplary degrees of decomposition test conditions are provided in U.S. Patent Nos. 5,970,988 and 6,571,802, the contents and disclosures of which are incorporated herein by reference.
[0127] In some embodiments, melt-processable plasticized cellulose ester composition can be a component of biodegradable disposable melt-molded article or can be used to prepare or form them.It has been found that melt-processable cellulose ester composition described herein can show an increased level of environmental non-persistence, characterized by better than expected decomposition under various environmental conditions.The melt-molded article described herein can meet or exceed one or more pass standards set by international testing methods and international organizations for industrial compostability, home compostability, marine biodegradability and / or soil biodegradability.
[0128] To be considered a "compostable" material, the following four criteria must be met: (1) the material must pass the biodegradation requirements corresponding to 90% absolute biodegradation or 90% relative biodegradation for a control polymer in a test according to ISO 14855-1 (2012) at elevated temperatures (58°C) under controlled composting conditions, (2) the material must reach 90% disintegration when tested according to ISO 16929 (2013) under aerobic composting conditions; (3) the test material must meet all requirements for volatile solids, heavy metals and fluorine as specified by ASTM D6400 (2012), EN 13432 (2000) and ISO 17088 (2012); (4) the material must not adversely affect plant growth. As used herein, the term "biodegradable" generally refers to the biological transformation and consumption of organic molecules. Biodegradability is an inherent property of the material itself, and materials may exhibit different degrees of biodegradability depending on the particular conditions to which they are exposed. The term "disintegrability" or phrase "degree of disintegration" refers to the tendency of a material to physically dissociate into smaller pieces when exposed to certain conditions. Disintegration depends on both the material itself, as well as the physical size and configuration of the article being tested. Ecotoxicity measures the effect of a material on plant life, and the heavy metal content of a material is determined in accordance with procedures set forth in standard test methods.
[0129] In one or more embodiments, the melt-processable plasticized cellulose ester compositions, melts and / or melt-formed articles of the present invention can be biodegradable. In one or more embodiments, the melts of the present invention can be biodegradable.
[0130] The melt processable cellulose ester composition (or melt or melt formed article) may exhibit at least 70 percent biodegradation in a period of 50 days or less when tested in accordance with ISO 14855-1 (2012) at ambient temperature (28° C.±2° C.) under aerobic composting conditions. In some cases, (or articles containing or formed therefrom) may exhibit at least 70 percent biodegradation in a period of 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, or 37 days or less when tested under these conditions, also referred to as "home composting conditions." These conditions may not be aqueous or anaerobic conditions. For some cellulose acetates, the melt-processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit a total biodegradation of at least about 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, or 88 percent when tested under home composting conditions for a period of 50 days or less in accordance with ISO 14855-1 (2012). This may represent a relative biodegradation of at least about 95, 97, 99, 100, 101, 102, or 103 percent when compared to cellulose subjected to similar test conditions.
[0131] To be considered "biodegradable", under home composting conditions, a material must show at least 90 percent total biodegradation (e.g., compared to the initial sample) or at least 90 percent of the maximum degradation of a suitable reference material after both the reference and test items reach a plateau, according to French Standard NF T 51-800 and Australian Standard AS 5810. Under home composting conditions, the maximum test duration for biodegradation is one year. The melt-processable plasticized cellulose ester compositions described herein may show at least 90 percent biodegradation within one year, measured under home composting conditions, according to 14855-1 (2012). For some cellulose acetates, the melt-processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit at least about 91, 92, 93, 94, 95, 96, 97, 98, 99, or 99.5 percent biodegradation within one year, or the cellulose acetate composition (or melt or melt-formed article) may exhibit 100 percent biodegradation within one year, as measured under home composting conditions in accordance with 14855-1(2012).
[0132] Additionally or alternatively, the melt processable plasticized cellulose ester compositions (or melt or melt formed articles) described herein may exhibit at least about 90 percent biodegradation within about 350, 325, 300, 275, 250, 225, 220, 210, 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, 100, 90, 80, 70, 60, or 50 days under home composting conditions in accordance with ISO 14855-1 (2012). In some embodiments, the compositions (or melt or melt formed articles) may be at least about 97, 98, 99, or 99.5 percent biodegradable within about 70, 65, 60, or 50 days under home composting conditions in accordance with ISO 14855-1 (2012). As a result, the composition (or articles containing or formed therefrom) may be considered biodegradable when tested under home composting conditions, for example, in accordance with French Standard NF T 51-800 and Australian Standard AS 5810.
[0133] The melt processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit at least 60 percent biodegradation in a period of 45 days or less when tested in accordance with ISO 14855-1 (2012) at a temperature of 58° C. (±2° C.) under aerobic composting conditions. In some cases, the melt processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit at least 60 percent biodegradation in a period of 44, 43, 42, 41, 40, 39, 38, 37, 36, 35, 34, 33, 32, 31, 30, 29, 28, or 27 days or less when tested under these conditions, also referred to as "industrial composting conditions." These may not be under aqueous or anaerobic conditions. In some cases, the melt-processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit a total biodegradation of at least about 65, 70, 75, 80, 85, 87, 88, 89, 90, 91, 92, 93, 94, or 95 percent when tested under industrial composting conditions for a period of 45 days in accordance with ISO 14855-1 (2012). This may represent a relative biodegradation of at least about 95, 97, 99, 100, 102, 105, 107, 110, 112, 115, 117, or 119 percent when compared to the same cellulose acetate composition (or melt or melt-formed article) subjected to similar test conditions.
[0134] To be considered "biodegradable," under industrial composting conditions, at least 90 percent of the organic carbon in the entire item (or for each component present in an amount greater than 1% by dry weight) must be converted to carbon dioxide by the end of the test period when compared to a control or absolute amount, in accordance with ASTM D6400 and ISO 17088.
[0135] In accordance with European Standard ED 13432 (2000), the material must exhibit at least 90 percent total biodegradation or at least 90 percent of the maximum degradation of a suitable reference material after both the reference and test items reach a plateau. Under industrial composting conditions, the maximum test duration for biodegradability is 180 days. The melt-processable plasticized cellulose ester compositions (or melt or melt-formed articles) described herein may exhibit at least 90 percent biodegradation within 180 days, measured under industrial composting conditions, in accordance with 14855-1 (2012). In some cases, the melt-processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit at least about 91, 92, 93, 94, 95, 96, 97, 98, 99, or 99.5 percent biodegradation within 180 days, or the cellulose acetate composition (or melt or melt-formed article) may exhibit 100 percent biodegradation within 180 days, as measured under industrial composting conditions in accordance with 14855-1(2012).
[0136] Additionally or alternatively, the melt processable plasticized cellulose ester compositions (or melt or melt molded articles) described herein may exhibit at least 90 percent biodegradation within about 175, 170, 165, 160, 155, 150, 145, 140, 135, 130, 125, 120, 115, 110, 105, 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, or 45 days, as measured under industrial composting conditions, per 14855-1(2012). In some cases, the melt-processable plasticized cellulose ester composition (or melt or melt-formed article) may be at least about 97, 98, 99, or 99.5 percent biodegradable within about 65, 60, 55, 50, or 45 days when tested under industrial composting conditions according to ISO 14855-1 (2012). As a result, the melt-processable plasticized cellulose ester composition (or melt or melt-formed article) described herein may be considered biodegradable when tested under industrial composting conditions according to ASTM D6400 and ISO 17088.
[0137] The melt-processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit at least 60 percent biodegradation in soil within 130 days, measured at ambient temperature under aerobic conditions, in accordance with ISO 17556 (2012). In some cases, the composition (or melt or melt-formed article) may exhibit at least 60 percent biodegradation within a period of 130, 120, 110, 100, 90, 80, or 75 days or less, when tested under these conditions, also referred to as "soil composting conditions". These may not be under aqueous or anaerobic conditions. In some cases, the composition (or melt or melt-formed article) may exhibit at least about 65, 70, 72, 75, 77, 80, 82, or 85 percent total biodegradation when tested under soil composting conditions for a period of 195 days, in accordance with ISO 17556 (2012). This may represent a relative biodegradation of at least about 70, 75, 80, 85, 90, or 95 percent when compared to the same composition (or melt or melt-formed article) subjected to similar test conditions.
[0138] To be considered "biodegradable", a material must exhibit at least 90 percent total biodegradation (e.g., compared to the initial sample) under soil composting conditions in accordance with Vincotte's OK Biodegradable SOIL Compatibility Mark and DIN CERTCO's DIN Gepruft Soil Biodegradability Certification Scheme, or at least 90 percent of the maximum degradation of a suitable reference material after both the reference and test items reach a plateau. Under soil composting conditions, the maximum test duration for biodegradability is 2 years. The melt-processible plasticized cellulose ester compositions described herein (or articles containing or formed therefrom) may exhibit at least 90 percent biodegradation within 2 years, 1.75 years, 1 year, 9 months, or 6 months, measured under soil composting conditions in accordance with ISO 17556 (2012). In some cases, the composition (or melt or melt formed article) may exhibit at least about 91, 92, 93, 94, 95, 96, 97, 98, 99, or 99.5 percent biodegradation within two years, as measured under soil composting conditions according to ISO 17556 (2012), or the composition (or melt or melt formed article) may exhibit 100 percent biodegradation within two years.
[0139] Additionally or alternatively, the melt processable plasticized cellulose ester compositions (or melt or melt formed articles) described herein may exhibit at least about 90 percent biodegradation within about 700, 650, 600, 550, 500, 450, 400, 350, 300, 275, 250, 240, 230, 220, 210, 200, or 195 days, as measured under soil composting conditions, in accordance with ISO 17556 (2012). In some cases, the compositions (or melt or melt formed articles) may be at least about 97, 98, 99, or 99.5 percent biodegradable within about 225, 220, 215, 210, 205, 200, or 195 days, as tested under soil composting conditions, in accordance with ISO 17556 (2012). As a result, the compositions (or melt or melt molded articles) described herein may meet the requirements to receive Vincotte's OK Biodegradable SOIL conformity mark and meet the standards of DIN CERTCO's DIN Gepruft soil biodegradability certification scheme.
[0140] In some embodiments, the cellulose ester composition (or melt or melt-formed article) of the present invention may contain less than 1, 0.75, 0.50, or 0.25 weight percent of unknown biodegradable components. In some cases, the composition (or melt or melt-formed article) described herein may not contain unknown biodegradable components.
[0141] In addition to being biodegradable under industrial and / or domestic composting conditions, the melt-processable plasticized cellulose ester compositions (or melt or melt-formed articles) described herein may also be compostable under domestic and / or industrial conditions. As previously described, a material is considered compostable if it meets or exceeds the requirements set forth in EN 13432 for biodegradability, disintegration ability, heavy metal content, and ecotoxicity. The compositions (or melt or melt-formed articles) described herein may exhibit sufficient compostability under domestic and / or industrial composting conditions and meet the requirements to receive the OK COMPOST and OK COMPOST HOME compatibility marks from Vincotte.
[0142] In some cases, the melt-processable plasticized cellulose ester compositions (or melt or melt-formed articles) described herein may have a volatile solids concentration, heavy metal and fluorine content that meets all the requirements set by EN 13432 (2000). In addition, the melt-processable plasticized cellulose ester compositions (or melt or melt-formed articles) may not adversely affect compost quality (including chemical parameters and ecotoxicity testing).
[0143] In some cases, the melt processable plasticized cellulose ester composition (or melt or melt formed article) may exhibit at least 90 percent disintegration within 26 weeks as measured under industrial composting conditions according to ISO 16929 (2013). In some cases, the melt processable plasticized cellulose ester composition (or melt or melt formed article) may exhibit at least about 91, 92, 93, 94, 95, 96, 97, 98, 99, or 99.5 percent disintegration within 26 weeks under industrial composting conditions, or the melt processable plasticized cellulose ester composition (or melt or melt formed article) may exhibit 100 percent disintegration within 26 weeks under industrial composting conditions. Additionally or alternatively, the melt processable plasticized cellulose ester composition (or melt or melt formed article) may exhibit at least 90 percent disintegration within about 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, or 10 weeks under industrial composting conditions, as measured according to ISO 16929 (2013). In some cases, the melt processable plasticized cellulose ester composition (or melt or melt formed article) described herein may exhibit at least 97, 98, 99, or 99.5 percent disintegration within 12, 11, 10, 9, or 8 weeks under industrial composting conditions, as measured according to ISO 16929 (2013).
[0144] In some embodiments, the melt processable plasticized cellulose ester composition (or melt or melt formed article) may exhibit at least 90 percent disintegration within 26 weeks as measured under home composting conditions according to ISO 16929 (2013). In some cases, the melt processable plasticized cellulose ester composition (or melt or melt formed article) may exhibit at least about 91, 92, 93, 94, 95, 96, 97, 98, 99, or 99.5 percent disintegration within 26 weeks under home composting conditions, or the composition (or melt or melt formed article) may exhibit 100 percent disintegration within 26 weeks under home composting conditions. Additionally or alternatively, the melt processable plasticized cellulose ester composition (or melt or melt-formed article) may exhibit at least 90 percent disintegration within about 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, or 15 weeks under home composting conditions, as measured according to ISO 16929 (2013). In some embodiments, the melt processable plasticized cellulose ester composition (or melt or melt-formed article) described herein may exhibit at least 97, 98, 99, or 99.5 percent disintegration within 20, 19, 18, 17, 16, 15, 14, 13, or 12 weeks under home composting conditions, as measured according to ISO 16929 (2013).
[0145] In an embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition, when melt-formed into a film having a thickness of 0.13, or 0.25, or 0.38, or 0.51, or 0.64, or 0.76, or 0.89, or 1.02, or 1.14, or 1.27, or 1.40, or 1.52 mm, exhibits greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929(2013). In certain embodiments, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76, or 0.89, or 1.02, or 1.14, or 1.27, or 1.40, or 1.52 mm, the film exhibits greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929(2013). In certain embodiments, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.13, or 0.25. or 0.38, or 0.51, or 0.64, or 0.76, or 0.89, or 1.02, or 1.14, or 1.27, or 1.40, or 1.52 mm, the film exhibits greater than 90, or 95, or 96, or 97, or 98, or 99% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929(2013).In certain embodiments, when the melt-processable plasticized cellulose ester composition is melt formed into a film having a thickness of 0.13, or 0.25, or 0.38, or 0.51, or 0.64, or 0.76, or 0.89, or 1.02, or 1.14, or 1.27, or 1.40, or 1.52 mm, the film exhibits greater than 90, or 95, or 96, or 97, or 98, or 99% disintegration after 8, or 9, or 10, or 11, or 12, or 13, or 14, or 15, or 16 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929(2013).
[0146] In some embodiments, the melt-processable plasticized cellulose ester composition (or melt or melt-molded article) described herein may be substantially free of photodecomposition agents.For example, the melt-processable plasticized cellulose ester composition (or melt or melt-molded article) may comprise about 1, 0.75, 0.50, 0.25, 0.10, 0.05, 0.025, 0.01, 0.005, 0.0025, or 0.001 weight percent or less of photodecomposition agents based on the total weight of the composition (or melt or melt-molded article), or the melt-processable plasticized cellulose ester composition (or melt or melt-molded article) may be free of photodecomposition agents.Examples of such photodecomposition agents include, but are not limited to, pigments that act as photooxidation catalysts and are optionally enhanced by the presence of one or more metal salts, oxidizable accelerators, and combinations thereof. The pigments may include coated or uncoated anatase or rutile titanium dioxide, which may be present alone or in combination with one or more enhancing components, such as, for example, various types of metals. Other examples of photodegradants include benzoin, benzoin alkyl ethers, benzophenone and its derivatives, acetophenone and its derivatives, quinones, thioxanthones, phthalocyanines, and other photosensitizers, ethylene-carbon monoxide copolymers, aromatic ketone-metal salt sensitizers, and combinations thereof.
[0147] In one aspect, there is provided a melt-formed biodegradable and / or compostable article comprising, formed from, or prepared using the melt-processable plasticized cellulose ester composition described herein. In an embodiment, the article is made from a moldable thermoplastic material comprising the melt-processable plasticized cellulose ester composition described herein.
[0148] In an embodiment, the melt-formed article is a disposable food contact article.Examples of such articles that can be made using the present composition include cups, trays, multi-compartment trays, clamshell containers, films, sheets, trays and lids (e.g., thermoformed), candy sticks, stirrers, straws, plates, deep dishes, portion cups, food packaging, liquid carriers, solid or gel carriers, and cutlery.In an embodiment, the melt-formed article can be a horticultural article.Examples of such articles that can be made using the melt-processable plasticized cellulose ester composition include flower pots, plant tags, mulch films, and agricultural ground covers.
[0149] In another aspect, a cellulose ester composition is provided, comprising recycled cellulose esters prepared by an integrated process, the process comprising the following processing steps: (1) preparing a recycled plastic-containing synthesis gas in a gas synthesis operation utilizing a feedstock containing a solid fossil fuel source and at least some content of recycled plastics; (2) preparing at least one chemical intermediate from the synthesis gas; (3) reacting the chemical intermediate in a reaction scheme to prepare at least one cellulose reactant for preparing recycled cellulose acetate and / or selecting the chemical intermediate as at least one cellulose reactant for preparing recycled cellulose acetate; and (4) reacting the at least one cellulose reactant to prepare the recycled cellulose ester, wherein the recycled cellulose ester comprises at least one substituent on anhydroglucose unit (AGU) derived from the recycled plastic-containing synthesis gas.
[0150] In an embodiment, processing steps (1)-(4) are carried out in a system that is in liquid and / or gaseous communication (i.e., including the possibility of a combination of liquid and gaseous communication). It will be appreciated that chemical intermediates may be temporarily stored in storage vessels and later reintroduced into the integrated process system in one or more reaction schemes to produce recycled cellulose acetate starting from recycled plastic-containing syngas.
[0151] In an embodiment, the at least one chemical intermediate is selected from methanol, methyl acetate, acetic anhydride, acetic acid, or a combination thereof. In an embodiment, one chemical intermediate is methanol, which is used in a reaction scheme to make a second chemical intermediate that is acetic anhydride. In an embodiment, the cellulose reactant is acetic anhydride.
[0152] In an embodiment, the melt processable plasticized cellulose ester composition comprises a cellulose ester, a plasticizer composition, and a stabilizer composition, the plasticizer composition comprising one or more food grade plasticizers and present in an amount of 5% to 30%, or 5% to 25%, or 5% to 20%, or 5% to 17%, or 5% to 15%, or 5% to 10% wt %, based on the total weight of the melt processable plasticized cellulose ester composition. If present, the optional stabilizer composition comprises one or more secondary antioxidants and present in an amount of 0.08 to 0.8, or 0.08 to 0.7, or 0.08 to 0.6 wt %, based on the total weight of the melt processable plasticized cellulose ester composition.
[0153] In an embodiment, the plasticizer composition comprises triacetin in an amount of 5-20 wt%, based on the total weight of the melt-processible plasticized cellulose ester composition; the optional stabilizer composition comprises one or more secondary antioxidants in an amount of 0.1-0.4, or 0.1-0.3 wt%, and one or more primary antioxidants in an amount of 0.1-0.4, or 0.2-0.4 wt%, where wt% is based on the total weight of the melt-processible plasticized cellulose ester composition. In one class of this embodiment, the one or more secondary antioxidants comprise a phosphite compound (e.g., Weston 705T or Doverphos S-9228T), DLTDP, or a combination thereof, and the one or more primary antioxidants comprise Irganox 1010, BHT, or a combination thereof. In embodiments, the melt processable plasticized cellulose ester composition has a b of less than 40, or less than 35, or less than 30, or less than 25, or less than 20, or less than 15 after normal cycles during injection molding. * or after a doubling cycle time during injection molding, a b of less than 40, or less than 35, or less than 30, or less than 25, or less than 20. * has.
[0154] In an embodiment, the plasticizer composition comprises a polyethylene glycol having an average molecular weight of 300 to 500 Daltons in an amount of 5% to 20% by weight based on the total weight of the melt-processible plasticized cellulose ester composition; the optional stabilizer composition comprises one or more secondary antioxidants in an amount of 0.01 to 0.8, or 0.1 to 0.5, or 0.1 to 0.3, or 0.1 to 0.2 wt %, based on the total weight of the melt-processible plasticized cellulose ester composition. In one class of this embodiment, the one or more secondary antioxidants comprise a phosphite compound (e.g., Weston 705T or Doverphos S-9228T), DLTDP, or a combination thereof. In another class of this embodiment, the stabilizer composition further comprises one or more primary antioxidants (e.g., Irganox 1010 or BHT), citric acid, or a combination thereof, where the one or more primary antioxidants are present in an amount of 0.1 to 0.5, or 0.1 to 0.4 wt %, based on the total weight of the melt-processible plasticized cellulose ester composition, and the citric acid is present in an amount of 0.05 to 0.2, or 0.05 to 0.15 wt %, based on the total weight of the melt-processible plasticized cellulose ester composition.
[0155] In embodiments, the plasticizer composition comprises polyethylene glycol of an average molecular weight of 300-500 Daltons in an amount of 5% to 20% or 5% to 17% or 5% to 16% or 5% to 15% by weight based on the total weight of the melt-processible plasticized cellulose ester composition; and the optional stabilizer composition comprises one or more secondary antioxidants in an amount of 0.1 to 0.5, or 0.1 to 0.3, or 0.1 to 0.2 wt %, based on the total weight of the melt-processible plasticized cellulose ester composition.
[0156] The present application also discloses a cellulose acetate composition, which comprises: (1) a degree of acetyl substitution ("DS") in the range of 2.2 to 2.6; Ac"), (2) 5-20 wt % of a polyethylene glycol or methoxypolyethylene glycol composition having an average molecular weight of 300 Daltons to 550 Daltons, and (3) a sulfonated isophthalic acid material, wherein the composition is melt processable and biodegradable, and articles comprising it, prepared with it or formed therefrom are biodegradable.
[0157] In one embodiment, or in combination with any other embodiment, the composition comprises polyethylene glycol having an average molecular weight of 300 to 500 daltons. In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition includes a polyethylene glycol having an average molecular weight of 350 to 550 Daltons.
[0158] In one embodiment, or in combination with any other embodiment, the cellulose acetate has a number average molecular weight ("Mn") in the range of 10,000 to 90,000 daltons, as measured by GPC. In one embodiment, or in combination with any other embodiment, the cellulose acetate has a number average molecular weight ("Mn") in the range of 30,000 to 90,000 daltons, as measured by GPC. In one embodiment, or in combination with any other embodiment, the cellulose acetate has a number average molecular weight ("Mn") in the range of 40,000 to 90,000 daltons, as measured by GPC.
[0159] In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.38 mm, the film shows more than 5% disintegration after 6 weeks and more than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.38 mm, the film shows more than 10% disintegration after 6 weeks and more than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.38 mm, the film shows more than 20% disintegration after 6 weeks and more than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.38 mm, the film shows more than 30% disintegration after 6 weeks and more than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.38 mm, the film exhibits greater than 50% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929(2013).In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition, when melt-formed into a film having a thickness of 0.38 mm, exhibits greater than 70% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929(2013).
[0160] In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film shows more than 30% disintegration after 12 weeks according to the disintegration test protocol described herein or according to the alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film shows more than 50% disintegration after 12 weeks according to the disintegration test protocol described herein or according to the alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film shows more than 70% disintegration after 12 weeks according to the disintegration test protocol described herein or according to the alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film exhibits greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film exhibits greater than 95% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013).
[0161] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition further comprises at least one additional component selected from a filler, an additive, a biopolymer, a stabilizer, or an odor modifier.
[0162] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition further comprises a filler in an amount of 1 to 60 wt %, based on the total weight of the composition. In a class of this embodiment, the filler is a carbohydrate, a cellulosic filler, an inorganic filler, a food by-product, a desiccant, an alkaline filler, or a combination thereof.
[0163] In a subclass of this class, the filler is an inorganic filler. In a sub-subclass of this subclass, the inorganic filler is calcium carbonate. In a subclass of this class, the filler is a carbohydrate.In a subclass of this class, the filler is a cellulosic filler.In a subclass of this class, the filler is a food by-product.In a subclass of this class, the filler is a desiccant.In a subclass of this class, the filler is an alkaline filler.
[0164] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition further comprises an odor modifying additive in an amount of 0.001 to 1 wt%, based on the total weight of the composition. In a class of this embodiment, the odor modifying additive is vanillin, Pennyroyal M-1178, almond, cinnamyl, spices, spice extracts, volatile organic compounds or small molecules, Plastidor, or combinations thereof. In a subclass of this class, the odor modifying additive is vanillin.
[0165] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition further comprises a stabilizer in an amount of 0.01 to 5 wt % based on the total composition. In one class of this embodiment, the stabilizer is a UV absorber, an antioxidant (e.g., ascorbic acid, BHT, BHA, etc.), an acid scavenger, a radical scavenger, an epoxidized oil (e.g., epoxidized soybean oil, epoxidized linseed oil, epoxidized sunflower oil), or a combination.
[0166] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition comprises a polyethylene glycol having an average molecular weight of 300 to 500 Daltons. In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition comprises a polyethylene glycol having an average molecular weight of 350 to 550 Daltons.
[0167] The present application also discloses articles, such as melt-molded articles, formed from or prepared using cellulose acetate compositions comprising the cellulose acetate compositions, the cellulose acetate compositions having: (1) a degree of acetyl substitution ("DS") in the range of 2.2 to 2.6; Ac "), (2) a 5-20 wt % polyethylene glycol or methoxypolyethylene glycol composition having an average molecular weight of 300 Daltons to 550 Daltons, and (3) a sulfonated isophthalic acid material, wherein the composition is melt processable and biodegradable.
[0168] In one embodiment, or in combination with any other embodiment, the article is formed from an orientation process, an extrusion process, an injection molding process, a blow molding process, or a thermoforming process. In a class of this embodiment, the article is formed from an orientation process. In a subclass of this class, the orientation process is a uniaxial extensional process or a biaxial extensional process.
[0169] In one class of this embodiment, the article is formed from an extrusion process. In one class of this embodiment, the article is formed from an injection molding process. In one class of this embodiment, the article is formed from a blow molding process. In one class of this embodiment, the article is formed from a thermoforming process. In a subclass of this class, the article comprises, is formed from, or is prepared using, a film or sheet having a thickness of from 0.25 mm (10 mils) to 4.06 mm (160 mils).
[0170] In one embodiment, or in combination with any other embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 10%. In one embodiment, or in combination with any other embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 8%. In one embodiment, or in combination with any other embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 6%. In one embodiment, or in combination with any other embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 5%. In one embodiment, or in combination with any other embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 4%. In one embodiment, or in combination with any other embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 3%. In one embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 2%. In one embodiment, or in combination with any other embodiment, when the article is a clear or transparent article, the article exhibits a turbidity of less than 1%.
[0171] In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film shows more than 30% disintegration after 12 weeks according to the disintegration test protocol described herein or according to the alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the composition is formed into a film having a thickness of 0.76 mm, the film shows more than 50% disintegration after 12 weeks according to the disintegration test protocol described herein or according to the alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film shows more than 70% disintegration after 12 weeks according to the disintegration test protocol described herein or according to the alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film exhibits greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the melt-processable plasticized cellulose ester composition is melt-formed into a film having a thickness of 0.76 mm, the film exhibits greater than 95% disintegration after 12 weeks according to the disintegration test protocol described herein or alternatively according to ISO 16929 (2013).
[0172] In one embodiment, or in combination with any other embodiment, the melt-formed article exhibits greater than 30% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the melt-formed article exhibits greater than 50% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the melt-formed article exhibits greater than 70% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the melt-formed article exhibits greater than 80% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the melt-formed article exhibits greater than 90% disintegration after 12 weeks according to the disintegration testing protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the melt-formed article exhibits greater than 95% disintegration after 12 weeks according to the disintegration testing protocol described herein or in accordance with an alternative ISO 16929 (2013).
[0173] In one embodiment, or in combination with any other embodiment, the melt-formed article has a thickness of 0.8 mm or less. In one embodiment, the melt-formed article has a thickness of 0.76 mm or less.
[0174] The present application also discloses an article comprising a cellulose acetate composition, the cellulose acetate composition comprising: (1) a cellulose acetate having a degree of acetyl substitution ("DSAc") in the range of 2.2 to 2.6; (2) 13 to 23 wt. % of a polyethylene glycol or methoxypolyethylene glycol composition having an average molecular weight of 300 Daltons to 550 Daltons; (3) a sulfonated isophthalic acid material; and (4) 0.01 to 1.8 wt. % of an additive selected from epoxidized soybean oil, a secondary antioxidant, or a combination, wherein the composition is melt processable, biodegradable, and disintegratable.
[0175] In one embodiment, or in combination with any other embodiment, the additive is present at 0.01-1 wt%, or 0.05-0.8 wt%, or 0.05-0.5 wt%, or 0.1-1 wt%.
[0176] In one embodiment, or in combination with any other embodiment, the additive is epoxidized soybean oil present at 0.1-1 wt%, or 0.1-0.5 wt%, or 0.5-1 wt%, or 0.3-0.8 wt%.
[0177] In one embodiment, or in combination with any other embodiment, the additive is a secondary antioxidant present at 0.01-0.8 wt%, or 0.01-0.4 wt%, or 0.4-0.8 wt%, or 0.2-0.6 wt%.
[0178] In one embodiment, or in combination with any other embodiment, the melt-processible plasticized cellulose ester composition comprises a polyethylene glycol having an average molecular weight of 300 to 500 Daltons. In one embodiment, or in combination with any other embodiment, the composition comprises a polyethylene glycol having an average molecular weight of 350 to 550 Daltons.
[0179] In one embodiment, or in combination with any other embodiment, the article is formed from an orientation process, an extrusion process, an injection molding process, a blow molding process, or a thermoforming process. In a class of this embodiment, the article is formed from an orientation process. In a subclass of this class, the orientation process is a uniaxial extensional process or a biaxial extensional process.
[0180] In one class of this embodiment, the article is formed from an extrusion process. In one class of this embodiment, the article is formed from an injection molding process. In one class of this embodiment, the article is formed from a blow molding process. In one class of this embodiment, the article is formed from a thermoforming process. In a subclass of this class, the film or sheet used to form the article is from 0.25 mm (10 mils) to 4.06 mm (160 mils) thick.
[0181] In one embodiment, or in combination with any other embodiment, when the composition is formed into a film having a thickness of 0.76 mm, the film exhibits greater than 30% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the composition is formed into a film having a thickness of 0.76 mm, the film exhibits greater than 50% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the composition is formed into a film having a thickness of 0.76 mm, the film exhibits greater than 70% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the composition, when formed into a film having a thickness of 0.76 mm, exhibits greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the composition, when formed into a film having a thickness of 0.76 mm, exhibits greater than 95% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013).
[0182] In one embodiment, or in combination with any other embodiment, the article exhibits greater than 30% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the article exhibits greater than 50% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the article exhibits greater than 70% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the article exhibits greater than 80% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the article exhibits greater than 90% disintegration after 12 weeks according to the disintegration testing protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the article exhibits greater than 95% disintegration after 12 weeks according to the disintegration testing protocol described herein or in accordance with an alternative ISO 16929 (2013).
[0183] In one embodiment, or in combination with any other embodiment, the article has a thickness of 0.8 mm or less. In one embodiment, the article has a thickness of 0.76 mm or less. In one or more embodiments, the melt-processable plasticized cellulose acetate composition of the present invention is a foamable composition.In one or more embodiments, the melt-processable plasticized foamable composition of the present invention comprises: (i) cellulose acetate; (ii) a plasticizer; (iii) a sulfonated isophthalic acid material; (iv) optionally at least one nucleating agent; and (v) at least one foaming agent selected from the group consisting of a physical foaming agent, a chemical foaming agent and a carrier polymer, and combinations thereof.
[0184] In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 100° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 102° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 104° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 106° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 110° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature of greater than 115° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa.
[0185] In one embodiment, or in combination with any other embodiment, the foaming agent comprises sodium bicarbonate, citric acid, or a combination thereof. In a class of this embodiment, the foaming agent comprises sodium bicarbonate. In a class of this embodiment, the foaming agent comprises citric acid.
[0186] In one embodiment, or in combination with any other embodiment, the carrier polymer comprises polybutylene succinate, polycaprolactone, or a combination thereof. In a class of this embodiment, the carrier polymer comprises polybutylene succinate. In a class of this embodiment, the carrier polymer comprises polycaprolactone.
[0187] In one embodiment, or in combination with any other embodiment, the plasticizer comprises triacetin, triethyl citrate, or PEG400. In one class of this embodiment, the plasticizer is present in the range from 3 to 30 wt %.In one class of this embodiment, the plasticizer is present in the range from 3 to 30 or 3 to 25 wt %.
[0188] In one class of this embodiment, the plasticizer comprises triacetin. In a subclass of this class, the plasticizer is present in the range 3 to 30 wt %. In a subclass of this class, the plasticizer is present in the range 3 to 30 or 3 to 25 wt %.
[0189] In one class of this embodiment, the plasticizer comprises triethyl citrate. In a subclass of this class, the plasticizer is present in the range of 3 to 30 wt %. In a subclass of this class, the plasticizer is present in the range of 3 to 30 or 3 to 25 wt %.
[0190] In one class of this embodiment, the plasticizer comprises PEG 400. In a subclass of this class, the plasticizer is present in the range of 3 to 30 wt %. In a subclass of this class, the plasticizer is present in the range of 3 to 30 or 3 to 25 wt %.
[0191] In one embodiment, or in combination with any other embodiment, the nucleating agent comprises magnesium silicate, silicon dioxide, magnesium oxide, or a combination thereof. In a class of this embodiment, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In a class of this embodiment, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. In a class of this embodiment, the nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0192] In one class of this embodiment, the nucleating agent comprises magnesium silicate. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0193] In one class of this embodiment, the nucleating agent comprises silicon dioxide. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0194] In one class of this embodiment, the nucleating agent comprises magnesium oxide. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0195] In one embodiment, or in combination with any other embodiment, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In one embodiment, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. The nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0196] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises fibers. In a class of this embodiment, the fibers comprise hemp, bast, jute, flax, ramie, kenaf, sisal, bamboo, or wood cellulose fibers. In a subclass of this class, the fibers comprise hemp.
[0197] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises a photodegradable cellulose catalyst. In a class of this embodiment, the photodegradable cellulose catalyst is titanium dioxide, or iron oxide. In a subclass of this class, the photodegradable cellulose catalyst is titanium dioxide. In a subclass of this class, the photodegradable cellulose catalyst is iron oxide.
[0198] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises a pigment. In a class of this embodiment, the pigment is titanium dioxide, cellulose carbon black, or iron oxide. In a subclass of this class, the pigment is titanium dioxide. In a subclass of this class, the pigment is cellulose carbon black. In a subclass of this class, the pigment is iron oxide.
[0199] In one embodiment, or in combination with any other embodiment, the foamable composition is biodegradable. In one embodiment, or in combination with any other embodiment, the foamable composition comprises two or more cellulose acetates having different degrees of acetyl substitution.
[0200] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises a biodegradable polymer different from cellulose acetate. In one embodiment, or in combination with any other embodiment, there is an article prepared from any one of the foamable compositions described hereinbefore, which article is a foam or foam article.
[0201] In one class of this embodiment, the article has a thickness up to 3 mm. In one class of this embodiment, the article has one or more skin layers. The skin layers may be found on the outer surface of the article or foam. Skin layer cellulose acetate may also be found in the middle of the foam.
[0202] In one class of this embodiment, the article is biodegradable. In one or more embodiments, particularly with respect to those embodiments in which the article is a foam or foam article, the density of the foam is an important parameter insofar as it can affect various article performance characteristics such as water barrier, stiffness, and thermal conductivity. In one class of this embodiment, the article has a density of 0.9 g / cm 3 or the article has a density of less than 0.9 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.8 g / cm 3 or the article has a density of less than 0.8 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.7 g / cm 3 or the article has a density of less than 0.7 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.6 g / cm 3 or the article has a density of less than 0.6 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.5 g / cm 3 or the article has a density of less than 0.5 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.4 g / cm 3 or the article has a density of less than 0.4 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.3 g / cm 3 or the article has a density of less than 0.3 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.2 g / cm 3 or the article has a density of less than 0.2 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.1 g / cm 3 or the article has a density of less than 0.1 g / cm 3In one class of this embodiment, the article includes a foam having a density of less than 0.05 g / cm 3 or the article has a density of less than 0.05 g / cm 3 In one class of this embodiment, the article includes a foam having a density of 0.2 to 0.9 g / cm 3 or the article has a density in the range of 0.2 to 0.9 g / cm 3 In one or more embodiments, the article comprises a foam having a density in the range of 0.01 to 0.2 g / cm 3 or the article has a density of 0.01 to 0.2 g / cm 3 The foam includes a foam having a density of
[0203] In one class of this embodiment, the article is industrially compostable or home compostable. In a subclass of this class, the article is industrially compostable. In a sub-subclass of this subclass, the article has a thickness of less than 1.1 mm. In a subclass of this class, the article is home compostable. In a sub-sub-subclass of this subclass, the article has a thickness of less than 1.1 mm. In a sub-sub-subclass of this subclass, the article has a thickness of less than 0.8 mm. In a sub-subclass of this subclass, the article has a thickness of less than 0.6 mm. In a sub-subclass of this subclass, the article has a thickness of less than 0.4 mm.
[0204] In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.38 mm, the foam exhibits greater than 5% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.38 mm, the foam exhibits greater than 10% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.38 mm, the foam exhibits greater than 20% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the composition is formed into a foam having a thickness of 0.38 mm, the foam exhibits greater than 30% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.38 mm, the foam exhibits greater than 50% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.38 mm, the foam exhibits greater than 70% disintegration after 6 weeks and greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013).
[0205] In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.76 mm, the foam exhibits greater than 30% collapse after 12 weeks according to the collapse test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.76 mm, the foam exhibits greater than 50% collapse after 12 weeks according to the collapse test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.76 mm, the foam exhibits greater than 70% collapse after 12 weeks according to the collapse test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.76 mm, the foam exhibits greater than 90% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, when the foamable composition is formed into a foam having a thickness of 0.76 mm, the foam exhibits greater than 95% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013).
[0206] In one or more embodiments, the invention can be a foamable composition that includes: (i) cellulose acetate; (ii) a plasticizer; (iii) a sulfonated isophthalic acid material; (iv) an optional nucleating agent; and (v) a foaming agent. In one or more embodiments, the foamable composition includes: (1) a degree of acetyl substitution (DS) of 2.2 to 2.6; Ac(2) 5-40 wt % of a plasticizer; (3) 0.1-3 wt % of a nucleating agent; and (4) 0.1-15 wt % of a physical foaming agent, where the proportions of cellulose acetate, plasticizer, nucleating agent and physical foaming agent are based on the total weight of the foamable composition. The foaming agent is preferably a physical foaming agent.
[0207] In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature (HDT) greater than 100° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 102° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 104° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 106° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 110° C., measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. In one embodiment, or in combination with any other embodiment, the foamable composition exhibits a heat deflection temperature greater than 115°C, measured using DMA at 2% elongation with a frequency of 1 Hz at 0.45 MPa. Heat deflection temperature is a measure of a material's resistance to strain at elevated temperature and constant load. For example, both ASTM D648 and ISO 75 measure the HDT (heat deflection temperature) on a test specimen after equilibration of the test material. Briefly, a test bar is molded with a specific thickness and width. The test specimen is submerged in oil where the temperature is increased at a constant rate (typically 2°C per minute). A load is applied to the midpoint of the test bar, which is supported near both ends. The temperature at which the bar of material deforms 0.25 mm is recorded as the HDT.
[0208] In one embodiment, or in combination with any other embodiment, the physical foaming agent is CO 2 , N2, unbranched or branched (C 2~6 ) alkanes, or any combination thereof. In one class of this embodiment, the physical foaming agent comprises CO 2 In one class of this embodiment, the physical foaming agent comprises N 2 In one class of this embodiment, the physical foaming agent comprises unbranched or branched (C 2~6 ) containing alkanes.
[0209] In one embodiment, or in combination with any other embodiment, the physical foaming agent is present at 0.1-0.5 wt%. In one embodiment, or in combination with any other embodiment, the physical foaming agent is present at 0.5-4 wt%. In one embodiment, or in combination with any other embodiment, the physical foaming agent is present at 0.3-4 wt%. In one embodiment, or in combination with any other embodiment, the physical foaming agent is present at 4-10 wt%.
[0210] In one embodiment, or in combination with any other embodiment, the plasticizer comprises triacetin, triethyl citrate, or PEG400. In one class of this embodiment, the plasticizer is present in the range from 3 to 30 wt.%.In one class of this embodiment, the plasticizer is present in the range from 3 to 25 wt.%, or 3 to 20 wt.%, or 3 to 15 wt.%.
[0211] In one class of this embodiment, the plasticizer comprises triacetin. In a subclass of this class, the plasticizer is present in the range 3 to 30 wt.%. In a subclass of this class, the plasticizer is present in the range 3 to 25 wt.% or 3 to 20 wt.% or 3 to 15 wt.%.
[0212] In one class of this embodiment, the plasticizer comprises triethyl citrate. In a subclass of this class, the plasticizer is present in the range of 3 to 30 wt.%. In a subclass of this class, the plasticizer is present in the range of 3 to 25 wt.% or 3 to 20 wt.% or 3 to 15 wt.%.
[0213] In one class of this embodiment, the plasticizer comprises PEG 400. In a subclass of this class, the plasticizer is present in the range of 3 to 30 wt.%. In a subclass of this class, the plasticizer is present in the range of 3 to 25 wt.% or 3 to 20 wt.% or 3 to 15 wt.%.
[0214] In one embodiment in which the foamable composition includes a nucleating agent, or in combination with any other embodiment, the nucleating agent includes magnesium silicate, silicon dioxide, magnesium oxide, or combinations thereof. In one class of this embodiment, the nucleating agent includes a particulate composition having a median particle size of less than 2 microns. In one class of this embodiment, the nucleating agent includes a particulate composition having a median particle size of less than 1.5 microns. In one class of this embodiment, the nucleating agent includes a particulate composition having a median particle size of less than 1.1 microns.
[0215] In one class of this embodiment, the nucleating agent comprises magnesium silicate. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0216] In one class of this embodiment, the nucleating agent comprises silicon dioxide. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0217] In one class of this embodiment, the nucleating agent comprises magnesium oxide. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. In a subclass of this class, the nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0218] In one embodiment, or in combination with any other embodiment, the nucleating agent comprises a particulate composition having a median particle size of less than 2 microns. In one embodiment, the nucleating agent comprises a particulate composition having a median particle size of less than 1.5 microns. The nucleating agent comprises a particulate composition having a median particle size of less than 1.1 microns.
[0219] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises fibers. In a class of this embodiment, the fibers comprise hemp, bast, jute, flax, ramie, kenaf, sisal, bamboo, or wood cellulose fibers. In a subclass of this class, the fibers comprise hemp.
[0220] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises a photolysis catalyst. In a class of this embodiment, the photolysis catalyst is titanium dioxide, or iron oxide. In a subclass of this class, the photolysis catalyst is titanium dioxide. In a subclass of this class, the photolysis catalyst is iron oxide.
[0221] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises a pigment. In a class of this embodiment, the pigment is titanium dioxide, cellulose carbon black, or iron oxide. In a subclass of this class, the pigment is titanium dioxide. In a subclass of this class, the pigment is carbon black. In a subclass of this class, the pigment is iron oxide.
[0222] In one embodiment, or in combination with any other embodiment, the foamable composition is biodegradable. In one embodiment, or in combination with any other embodiment, the foamable composition comprises two or more cellulose acetates having different degrees of acetyl substitution.
[0223] In one embodiment, or in combination with any other embodiment, the foamable composition further comprises a biodegradable polymer different from cellulose acetate. In one embodiment, or in combination with any other embodiment, there is an article prepared from any one of the foamable compositions described hereinbefore, the article being a foam or foam article. In one or more embodiments, the foam article is formed from or includes a foam of the present invention.
[0224] In one class of this embodiment, the article has a thickness or foam thickness up to 3 mm. In one class of this embodiment, the article has one or more skin layers.
[0225] In one class of this embodiment, the article is a melt-formed article which may be one or more of biodegradable, disintegrable and compostable. In one class of this embodiment, the article has a hardness of 0.9 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.8 g / cm 3 or the article has a density of less than 0.8 g / cm 3In one class of this embodiment, the article includes a foam having a density of less than 0.7 g / cm 3 or the article has a density of less than 0.7 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.6 g / cm 3 In one class of this embodiment, the article has a density of less than 0.5 g / cm 3 or the article has a density of less than 0.5 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.4 g / cm 3 or the article has a density of less than 0.4 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.3 g / cm 3 or the article has a density of less than 0.3 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.2 g / cm 3 or the article has a density of less than 0.2 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.1 g / cm 3 or the article has a density of less than 0.1 g / cm 3 In one class of this embodiment, the article includes a foam having a density of less than 0.05 g / cm 3 or the article has a density of less than 0.05 g / cm 3 In one class of this embodiment, the article includes a foam having a density of 0.2 to 0.9 g / cm 3 It has a density in the range of
[0226] In one class of this embodiment, the article is industrially compostable or home compostable. In a subclass of this class, the article is industrially compostable. In a sub-subclass of this subclass, the article has a thickness of less than 6 mm. In a sub-subclass of this subclass, the article has a thickness of less than 3 mm. In a sub-subclass of this subclass, the article has a thickness of less than 1.1 mm. In a subclass of this class, the article is home compostable. In a sub-subclass of this subclass, the article has a thickness of less than 6 mm. In a sub-subclass of this subclass, the article has a thickness of less than 3 mm. In a sub-subclass of this subclass, the article has a thickness of less than 1.1 mm. In a sub-subclass of this subclass, the article has a thickness of less than 0.8 mm. In a sub-subclass of this subclass, the article has a thickness of less than 0.6 mm. In a sub-subclass of this subclass, the article has a thickness of less than 0.4 mm.
[0227] In one embodiment, or in combination with any other embodiment, the article has a thickness of less than 6 mm. In one embodiment, or in combination with any other embodiment, the article has a thickness of less than 3 mm. In one embodiment, or in combination with any other embodiment, the article has a thickness of less than 1.1 mm. In one embodiment, or in combination with any other embodiment, the article has a thickness of less than 0.8 mm. In one embodiment, or in combination with any other embodiment, the article has a thickness of less than 0.6 mm. In one embodiment, or in combination with any other embodiment, the article has a thickness of less than 0.4 mm.
[0228] The present application relates to a method for producing a foamable composition comprising: (a) providing a non-foamable composition comprising: (1) a cellulose acetate having a degree of acetyl substitution (DSAc) of 2.2 to 2.6; (2) 5 to 40 wt % of a plasticizer; and (3) 0.1 to 3 wt % of a nucleating agent; (b) melting the non-foamable composition in an extruder to form a melt of the non-foamable composition; and (b) injecting a physical foaming agent into the melt of the non-foamable composition to prepare a molten foamable composition. A method for preparing a foamable composition is disclosed, comprising:
[0229] In one embodiment, or in combination with any other embodiment, the physical foaming agent is CO 2 , N 2 , or unbranched or branched (C 2~6 ) containing alkanes. In one embodiment, or in combination with any other embodiment, the foam or foam article exhibits greater than 30% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the foam or foam article exhibits greater than 50% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the foam or foam article exhibits greater than 70% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the foam or foam article exhibits greater than 80% disintegration after 12 weeks according to the disintegration test protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the foam or article exhibits greater than 90% disintegration after 12 weeks according to the disintegration testing protocol described herein or in accordance with an alternative ISO 16929 (2013). In one embodiment, or in combination with any other embodiment, the foam or article exhibits greater than 95% disintegration after 12 weeks according to the disintegration testing protocol described herein or in accordance with an alternative ISO 16929 (2013).
[0230] The present invention shows many surprising features and achieves many unexpected performance and processing parameters.The plasticized cellulose ester composition of the present invention can show improved melt strength and melt viscosity and desirable shear thinning while maintaining the physical properties and characteristics of cellulose ester.Another particular point of interest is the improvement / increase in area (flat) stretch ratio, which leads to improved extensibility in the application of melt-formed thermoplastics such as film and the formation of thermoformed articles such as cups with greater depth.
[0231] The melt strength observed in the present invention may be useful in foam articles or foaming processes where melt strength is desired, such as, for example, blown film, extrusion blow molding, minimizing sag in thermoforming and extrusion, and adjusting cell size in foaming. Interestingly, the compositions of the present invention also show improved strain hardening over a control that does not contain aromatic sulfonate repeat units. Furthermore, the plasticized cellulose ester compositions of the present invention show improved char formation over the control, suggesting a flame retardant / flame resistant advantage. Surprisingly, even though the sulfoisophthalic acid material may be water dispersible, it was observed that less than 10 ppm of the sulfoisophthalic acid material migrated when exposed to an aqueous solution at 70°C for 2 hours. Finally, the sulfoisophthalic acid material may be water dispersible, thus serving as a disintegration enhancer and allowing for higher compostable thickness. These and other benefits and advantages of the present invention are demonstrated in the examples set forth below, which are provided merely as illustrations of embodiments of the present invention and are not intended to limit the spirit and scope of the present invention. Detailed embodiment Embodiment 1. A melt-processible plasticized cellulose ester composition comprising: (i) a cellulose ester; (ii) a plasticizer; and (iii) a polymer comprising aromatic sulfonate repeat units. Embodiment 2. The melt-processible plasticized cellulose ester composition of embodiment 1, wherein the plasticizer is present in an amount of 1% to 40% by weight, based on the total weight of the melt-processible plasticized cellulose acetate composition. Embodiment 3. The melt-processible plasticized cellulose ester composition of embodiment 1 or 2, wherein the polymer comprising aromatic sulfonate repeat units is present in an amount of 0.1 wt% to 50.0 wt% by weight, based on the total weight of the melt-processible plasticized cellulose ester composition. Embodiment 4. The melt-processible plasticized cellulose ester composition of any one of embodiments 1-3, wherein the aromatic sulfonate repeat units are present in the polymer in an amount from 1 mol % to 50 mol %. Embodiment 5. The melt-processable plasticized cellulose ester composition of any one of claims 1-4, wherein the cellulose ester comprises cellulose acetate. Embodiment 6. The melt-processible plasticized cellulose ester composition of any one of embodiments 1-5, wherein the aromatic sulfonate repeat units comprise sulfonated isophthalic acid residues or salts thereof. Embodiment 7. The melt-processible plasticized cellulose ester composition of any one of embodiments 1-6, wherein the polymer comprises a sulfonated polyester. Embodiment 8. The sulfonated polyester has the formula:
[0232] [ka]
[0233] wherein M is a cation selected from the group consisting of Li, Na, Ca, K, Zn and Mg. 8. The melt-processible plasticized cellulose ester composition of embodiment 7, comprising an aromatic sulfonate repeat unit of Embodiment 9. The melt-processible plasticized cellulose ester composition of embodiment 7, wherein the sulfonated polyester is characterized by one or more of a glass transition temperature of -60 to 100°C, an intrinsic viscosity of 0.05 to 0.80 dL / g. Embodiment 10. The melt-processible plasticized cellulose ester composition of embodiment 7, wherein the sulfonated polyester is characterized by one or more of a glass transition temperature of 35-38° C., an intrinsic viscosity of 0.32-0.40 dL / g, an acid number of less than 2 mg KOH / g, and a hydroxyl number of less than 10 mg KOH / g.
[0023] Embodiment 11. The sulfonated polyester has a glass transition temperature of 51 to 55°C, an intrinsic viscosity of 0.29 to 0.37 dL / g, an acid number of less than 2 mg KOH / g, a hydroxyl number of less than 10 mg KOH / g, and a viscosity of 814.8 kg / m 3(6.8 pounds / gallon) or less. Embodiment 12. The melt-processible plasticized cellulose ester composition of any one of embodiments 1 to 11, exhibiting a strain hardening ("SH") in the range of 10% to 150%, or 30% to 150%, or 50% to 150%, or 70% to 150%, or 90% to 150%, or 110% to 150% compared to a melt-processible cellulose ester composition not comprising a polymer comprising aromatic sulfonate repeat units, wherein the SH is determined by the procedure disclosed herein. Embodiment 13. The melt-processible plasticized cellulose ester composition of any one of embodiments 1 to 12, exhibiting a maximum areal draw ratio ("Max ADR") in the range of 10% to 50%, or 20% to 50%, or 30% to 50%, or 40% to 50% compared to a melt-processible cellulose ester composition not comprising a polymer comprising aromatic sulfonate repeat units, the Max ADR being determined by the procedure disclosed herein. Embodiment 14. A cellulose ester melt comprising, formed from, or prepared using the melt-processible plasticized cellulose ester composition of any one of embodiments 1-13. Embodiment 15. A melt molded article comprising, formed from, or prepared using the melt-processible plasticized cellulose ester composition of any one of embodiments 1-13 or the cellulose ester melt of claim 14. Embodiment 16. The article of embodiment 15, which is an injection molded article. Embodiment 17. The article of embodiment 15, which is a compression molded article. Embodiment 18. The article of embodiment 15, which is an extruded article. Embodiment 19. The article of embodiment 15, which is a profiled extrusion article. Embodiment 20. The article of embodiment 15, which is a thermoformed article. Embodiment 21. An article comprising a foam formed from or prepared using the melt-processible plasticized cellulose ester composition according to any one of embodiments 1-13 or the cellulose ester melt according to embodiment 14. EXAMPLES
[0234] The following materials were utilized in carrying out the examples set forth below, with the abbreviations for the materials being indicated in parentheses. All percentages in the examples are by weight based on the total weight of the composition, unless otherwise indicated.
[0235] Cellulose ester (CE): Cellulose diacetate (CDA) with degree of substitution (DS) = 2.52, melting point of 230-250°C and Tg = 189°C. Available commercially as CA-398-30 from Eastman Chemical Company. Plasticizers: Triacetin (TA), Polyethylene Glycol 400 (PEG400) Polymers with aromatic sulfonate repeat units: Water-dispersible, sulfonated polyesters (SFPs) with ionic monomers, 5-20 wt % sulfoisophthalic acid SIPA; listed below as SFP1, SFP2, and SFP3. SFP1 and SFP2 are commercially available from Eastman Chemical Company as AQ-38 and AQ-55, respectively, and are described elsewhere herein.
[0236] The plasticized cellulose ester composition of the present invention was formed into pellets through compounding. An 18 mm Leistritz twin screw extruder with a single hole die and screw design was used to extrude the pellets, which were then used later for film extrusion. These pellets were made from raw materials consisting of powder (CA 398-30), liquid plasticizer (TA) and one of the above sulfonated polyesters added as pellets. The plasticizer was fed to zone 2 by a liquid injection unit equipped with a Witte gear pump, a Hardy 4060 regulator, and an injector with a 0.508 mm (0.020 inch) aperture. The compounded strand was passed through a water trough and pelletized using a ConAir pelletizer.
[0237] Typical extruder conditions are detailed in Table 1 below.
[0238] [Table 1]
[0239] The composition details are set out in Table 2 below:
[0240] [Table 2]
[0241] 0.76 mm (30 mil) thick films were extruded using a 3.8 cm (1.5 inch) Killion extruder. Example film extrusion conditions are as follows:
[0242] [Table 3]
[0243] Melt Rheology. Films from formulations C2 and A7 above were then analyzed by melt rheology to estimate the melt viscosity. Film samples were tested on an ARES-G2 rotational rheometer using a circular parallel plate geometry with a 1 mm gap. Logarithmic frequency sweep tests were performed using a constant deformation strain of 10% over the range of 1-400 rad / sec (5 pt / decade) at a constant temperature of 220°C. In general, low shear rates may correspond to processes such as compounding, while high shear rates may correspond to processes such as injection molding. The results are shown in Table 4 below.
[0244] [Table 4]
[0245] Shear thinning was quantified as the ratio of the change in viscosity divided by the change in angular frequency, relative to the control, and is shown in Table 5 below:
[0246] [Table 5]
[0247] Film Stretching / Thermoforming. Selected films (from formulations C1, A1, A2, A5 and A6) were stretched in a biaxial film stretcher at different temperatures and strain rates. More specifically, the films were stretched in a biaxial stretcher at 185°C using a strain rate of 50% and a 2x2 stretch ratio. A 2x2 stretch is a 2x stretch along the length and width of the film / sheet using a biaxial stretcher. The ratio of the film area after stretching and before stretching is referred to as the planar stretch ratio. In this test, a planar stretch ratio of 4 is utilized.
[0248] From visual observation, the control film from sample C1 had significant hole defects. The films from samples A1, A2, A5 and A6 showed no or minimal hole defect size, and in particular, no hole defects were visible for A6. This data illustrates the improvement in extensibility of the compositions and articles of the present invention.
[0249] Plug-Assist Thermoforming. To further determine extensibility, plug-assisted thermoforming experiments were performed using a Comet (Model C64S). A multi-cavity mold with nine cavities was used to thermoform the film. Each cavity has a different depth simulating an areal stretch ratio ranging from 1.5 to 5.5 in 0.5 increments. The areal stretch ratio ("ADR") or stretch ratio is the ratio of the surface area of the part after thermoforming to the surface area before thermoforming. The plug speed was held constant at 1.40 cm / min (0.55 in / min) and the mold temperature was measured during each run. The sheet temperature was held at Tg (glass transition) + 75°C.
[0250] [Table 6]
[0251] The increase in maximum achievable stretch ratio is analogous to an increase in extensibility. The reduction in sag is analogous to an increase in melt strength. Comparing compound C2 to A2, the maximum ADR increased from 2.0 to 4.0, and the sag decreased from about 161 mm to about 125 mm. Similarly, comparing compound C3 to A8, the maximum ADR increased from 4.0 to 5.5, and the sag was similar or slightly increased from about 181 mm to about 187 mm.
[0252] To further determine extensibility, thermoforming experiments were performed using a multi-cavity mold with different stretch ratios using a vacuum-only thermoformer. Measurements were performed using a mold with cups at selected planar stretch ratios ranging from 1.5 to 5.5. 0.76 mm (30 mil) films from samples A1, A2, A5, and A6 were thermoformed using the following conditions: oven temperature of 288°C (550°F), sheet temperature of 204°C (400°F), and cycle time of 36 seconds.
[0253] The extensibility of the films evaluated via thermoforming was generally similar to that of the films evaluated via a biaxial stretcher. Films from A1, A2, A5, and A6 stretched very well with uniform material distribution (bottom thickness - 19 mils) at planar stretch ratios of 3.0 and 3.5. Films were also successfully formed into parts at a planar stretch ratio of 4.0, but the material distribution was not uniform (thin bottom). Film from sample C1 was successfully formed into parts at the maximum planar stretch ratio of 3.0, attempts at higher planar stretch ratios were unsuccessful as indicated by poor material distribution, thinner films, and even failure to form holes.
[0254] Char Formation. Portions of the film samples from compositions C1 and A1-A6 were evaluated for char formation by heating and measuring weight loss. Using a thermogravimetric analyzer (TGA), the samples were heated to 600° C. at 20° C. / min and the weight loss was measured as a function of temperature in percentage, with the remaining weight considered as char. The results are shown in Table 7 below:
[0255] [Table 7]
[0256] The data above showed a 1.5-fold increase in char formation for Samples A1-A6 over Control C1. A slight increase in char formation was also generally observed as the concentration of sulfoisophthalic acid material increased. Increased char formation can generally be an indicator of utility in a flame retardant composition.
[0257] SFP migration. Films from compositions C1, A1, A2 and A4-A6 were immersed in 10% aqueous EtOH solution at 70°C for 2 hours. ICP (inductively coupled plasma) spectroscopy was used to measure the sulfur (S) content in the solutions. From the test protocol involving films from compositions containing sulfoisophthalic acid materials, no significant differences in the S content in the test solutions were observed (less than 10 ppm).
[0258] Compostability and Disintegration. Samples (in pellet form) of the sulfoisophthalic acid material utilized to form Samples A1-A6 were immersed in an aqueous solution maintained at 70° C. for two weeks. These conditions were chosen to generally mimic an industrial composting environment, which is typically ∼60° C. Molecular weights of pellet samples were measured via gel permeation chromatography using NMP / 0.3 LiBr solvent before and after water treatment, and PS equivalents were calculated. The results are shown in Table 8 below.
[0259] [Table 8]
[0260] The samples were significantly hydrolyzed (>60% reduction in weight average molecular weight) at the selected temperatures, suggesting that SFP is industrially compostable within most standard tests for industrial composting, which typically include measurement periods of 3–6 months.
[0261] To determine the disintegratability of the compositions, 1.52 mm (60 mil) film plaques of samples C1, A2, A4 and A6 were immersed in deionized water for one week at room temperature. Plaques from A2, A4 and A6 showed significant blisters while the control showed no visible difference, suggesting that films from the compositions of the present invention will disintegrate faster in an industrial composting environment. thermoforming 0.76 mm (30 mil) extruded films compounded with 20 wt% PEG400 (plasticizer) and 1-10 wt% ionic polymer additive (S112 sulfopolyester) were thermoformed in a Comet Model C64S thermoformer by male plug assisted vacuum forming. The mold was a multi-cavity mold with nine cylindrical cups arranged in a 3 x 3 grid. Each cup was 5.1 cm (2 inches) in diameter while the depth varied from 0.64 cm (1 / 4 inch) to 5.7 cm (2 1 / 4 inches), resulting in an areal draw ratio (ADR) ranging from 1.5 to 5.5. The male plug was designed to provide a 100 pm clearance between the female and male dies. Each extruded sheet was clamped on two sides and heated to a target sheet temperature of Tg + 75 °C. The resulting sheet surface temperature (°C), sag (mm) and maximum areal draw ratio (ADR) were recorded in replicates for each sample and averaged and summarized in Table 9. Sheet temperature was recorded at several points across the sheet using an IR thermometer located directly above the clamping frame. Sag was measured using a GoPro camera rig calibrated from the bottom of the clamping frame to the lowest point of the sagging sheet. Sheets that had no visible sag below the bottom of the clamping frame were recorded as <125mm because the clamping frame prevented the camera from viewing the initial gap of approximately 125mm between the clamped sheet and the bottom of the clamping frame. For the purposes of this test, maximum ADR was defined and recorded as the ADR in the mold cavity where the cup formed without any visible defects such as stress whitening, discoloration, tears, or / holes. From the table below, it is clear that the addition of 1-10 wt% of an ionic polymer additive (S112 sulfopolyester) significantly increases the maximum ADR achieved ("Max ADR") compared to samples using only plasticizer (PEG400).
[0262] [Table 9]
[0263] Elongation rheology data The uniaxial extensional flow properties of 0.76 mm (30 mil) extruded film samples compounded with 20 wt% PEG400 (plasticizer) and 1-10 wt% ionic polymer additive (S112 sulfopolyester) were characterized on a TA Instruments ARES-G2 rotational rheometer equipped with a Sentmanat Extensional Rheometer (SER) fixture, consisting of two counter-rotating drums with intermeshing gears and low friction bearings. Specimens measuring 76.2 mm (3 in) in length and 12.7 mm (0.5 in) in width were cut from the extruded film and secured at both ends using fixed clamps to two drums set at the desired test temperature. The test temperature used was determined to be Tg+75°C, similar to the thermoforming temperature. Rotation of the rheometer drive shaft rotates the drums in opposite directions, which causes the ends of the specimen film to wrap around the drums, thus stretching the specimen film uniformly over its unsupported extended length. The specimen film was stretched at a constant rate until it broke, and the torque and axial force data from the rheometer were converted to extensional viscosity, which is the Hencky strain (ε H ) or plotted as a function of time. Extensional rheological testing allows for the quantification of strain hardening properties, which provides direct insight into the melt strength and melt extensibility characteristics of polymeric materials. The strain hardening index (SH) is calculated using the following equation: SH=η E / 3η 0 [In the formula, η E (Pa.s) is the Hencky strain (ε H The apparent extensional viscosity was determined using the peak of the extensional viscosity curve as a function of η. 0 is the zero-shear viscosity measured by means of a dynamic frequency sweep experiment using a parallel plate fixture on a rotational rheometer. Table 10 shows the η for samples with and without an ionic polymer additive (S112 sulfopolyester). 0 , ε H , η Eand SH values are listed. It is clear that the addition of 1-10 wt% ionic polymer additive (S112 sulfopolyester) significantly increases the strain hardening (SH) when compared to the plasticizer (PEG400) only control sample, which correlates well with the maximum ADR data obtained from thermoforming.
[0264] [Table 10]
Claims
1. A melt-processible plasticized cellulose ester composition comprising: (i) a cellulose ester; (ii) a plasticizer; and (iii) a polymer that includes aromatic sulfonate repeat units.
2. 2. The melt-processible plasticized cellulose ester composition of claim 1, wherein the plasticizer is present in an amount of from 1% to 40% by weight, based on the total weight of the melt-processible plasticized cellulose acetate composition.
3. 3. The melt-processible plasticized cellulose ester composition of claim 1, wherein the polymer containing aromatic sulfonate repeat units is present in an amount of 0.1 wt % to 50.0 wt % by weight, based on the total weight of the melt-processible plasticized cellulose ester composition.
4. 4. The melt-processible plasticized cellulose ester composition of claim 1, wherein the aromatic sulfonate repeat units are present in the polymer in an amount of from 1 mol % to 50 mol %.
5. 5. The melt-processible plasticized cellulose ester composition of claim 1, wherein the cellulose ester comprises cellulose acetate.
6. 6. The melt-processible plasticized cellulose ester composition of claim 1, wherein the polymer comprises a sulfonated polyester.
7. The sulfonated polyester has the formula: 【Chemistry 1】 wherein M is a cation selected from the group consisting of Li, Na, Ca, K, Zn and Mg.
7. The melt-processible plasticized cellulose ester composition of claim 6, comprising aromatic sulfonate repeat units of the formula:
8. 8. The melt-processible plasticized cellulose ester composition of claim 6 or 7, wherein the sulfonated polyester is characterized by one or more of a glass transition temperature of -60 to 100°C, an intrinsic viscosity of 0.05 to 0.80 dL / g.
9. 8. The melt processable plasticized cellulose ester composition of claim 6 or 7, wherein the sulfonated polyester is characterized by one or more of a glass transition temperature of 35-38° C., an intrinsic viscosity of 0.32-0.40 dL / g, an acid number of less than 2 mg KOH / g, and a hydroxyl number of less than 10 mg KOH / g.
10. The sulfonated polyester has a glass transition temperature of 51-55° C., an intrinsic viscosity of 0.29-0.37 dL / g, an acid number of less than 2 mg KOH / g, a hydroxyl number of less than 10 mg KOH / g, and a viscosity of 814.8 kg / m 3 8. The melt processable plasticized cellulose ester composition of claim 6, characterized by one or more of the following bulk densities:
11. 11. The melt-processible plasticized cellulose ester composition of any one of claims 1 to 10, wherein the melt-processible plasticized cellulose ester composition exhibits a strain hardening ("SH") in the range of 10% to 150%, or 30% to 150%, or 50% to 150%, or 70% to 150%, or 90% to 150%, or 110% to 150% compared to a melt-processible cellulose ester composition not comprising a polymer comprising aromatic sulfonate repeat units, wherein the SH is determined by the procedure disclosed herein.
12. 12. The melt-processible plasticized cellulose ester composition of any one of claims 1 to 11, exhibiting a maximum areal draw ratio ("Max ADR") ranging from 10% to 50%, or 20% to 50%, or 30% to 50%, or 40% to 50% compared to a melt-processible cellulose ester composition not comprising a polymer comprising aromatic sulfonate repeat units, the Max ADR being determined by the procedure disclosed herein.
13. 13. A cellulose ester melt comprising, formed from or prepared using the melt-processible plasticized cellulose ester composition of any one of claims 1 to 12.
14. 14. A melt molded article comprising, formed from, or prepared using the melt processable plasticized cellulose ester composition of any one of claims 1 to 12 or the cellulose ester melt of claim 13.
15. 15. The article of claim 14 which is an injection molded article.
16. 15. The article of claim 14 which is a compression molded article.
17. 15. The article of claim 14 which is an extruded article.
18. 15. The article of claim 14 which is a profiled extrusion article.
19. 15. The article of claim 14 which is a thermoformed article.
20. 14. An article comprising a foam formed from or prepared using the melt-processible plasticized cellulose ester composition of any one of claims 1 to 12 or the cellulose ester melt of claim 13.